GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 171683478 species occurrences available in GBIF matching the query: TaxonKey: Plantae or Manihot brachyloba Müll.Arg.. The dataset includes 171683478 records from 3129 constituent datasets: 41 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3565 records from Bioimages. 22 records from Naturalis Biodiversity Center (NL) - Crustacea. 8934 records from El género Bursera en México. Parte II. 15300 records from Base de datos de colecciones de maíces nativos, teocintles y Tripsacum de México. 142 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 1348 records from Inventory of Wari maro forest (Benin). 926 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 1093 records from National Biodiversity Data Bank. Observation records, 1900-2014. 113598 records from Merseyside BioBank (unverified). 3104 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 2175 records from Invasión de Pinus spp y la conservación de la diversidad florística en Los Altos de Chiapas, México. 162181 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 5952 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 838 records from Asociación de cactáceas con arbustos en el desierto costero de Topolobampo, Sinaloa. 2 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10043 records from Guadeloupe_Herbier. 3 records from Plan de vertebrados de la Patagonia. 11334 records from International Barcode of Life project (iBOL). 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 44 records from Complete list of isolated phyllosphere Methylobacterium strains. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 80 records from Pepper French national collection. 12855 records from JOI - Herbário Joinvillea. 14894 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1650 records from University of Calgary Herbarium. 635 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 3323794 records from OEH Atlas of NSW Wildlife. 2785 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 712 records from Aprovechamiento sustentable y conservación de la palma bola (Zamia furfuracea), especie endémica protegida, en la zona de Los Tuxtlas, Veracruz. 3401969 records from A global database for the distributions of crop wild relatives. 5774 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 168961 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1850 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 23409 records from HUEM - Herbário da Universidade Estadual de Maringá. 5525 records from Bryophyte diversity in grassland. 70493 records from HUFU - Herbarium Uberlandense. 2497 records from InsectScale2008FlowerCover. 1018240 records from Phanerogamic Botanical Collections (S). 105082 records from Jordal. 42 records from MVZ Herp Collection (Arctos). 190 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 236 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 62282 records from PRECIS (KwaZulu-Natal Herbarium). 712 records from Herbier G. Garapin (BOUM). 82159 records from University of Vienna, Institute for Botany - Herbarium WU. 1950 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 16657 records from UFG - Herbário da Universidade Federal de Goiás. 1702 records from BioGIS - Bryophytes - HUJ collections. 5962 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 653 records from Colección nacional de palmas de Colombia - JBQ. 39 records from Lindesnes. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 1800 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 40 records from Monitoreo del bentos, nutrientes e isótopos en relación a la salud arrecifal de áreas naturales protegidas del norte de Quintana Roo con mayor vulnerabilidad al cambio de fase arrecifal: Primera Etapa. 147 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 1 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 56570 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 29 records from Coastal and marine species. 10336 records from Census of the flora of Benin. 3896 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 142495 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 23088 records from Bryophyte herbarium, Tromsø Museum. 175 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 40 records from Ecología evolutiva de dos especies invasoras de humedales en la República Mexicana: Arundo donax y Phragmites australis (Poaceae). 34 records from New records in vascular plants alien to Kyrgyzstan. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 56709 records from Online Atlas of vascular plants 2012-2020. 12361 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 53364 records from IAC - Herbário do Instituto Agronômico de Campinas. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 504 records from Flora leñosa de la reserva La Selva El Ocote. 38816 records from Bryophyte diversity in forests. 104 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1 records from Fossil (SMNH-FO). 359 records from Base de datos de las cicadas mexicanas. 12 records from Palaeobiology collection, FAU Erlangen. 49930 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 122986 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 2989 records from Portuguese Seaweeds. 2450 records from HBRG Fungus, Lichen & Lower Plants Dataset. 1 records from Collection of Heteroptera. 152 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México: 3a fase. 176 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2533 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 86 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 35306 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 4577 records from Herbarium WRSL, Flora of the Silesia. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 1064 records from Bryophytes, fungi and lichens on dead wood. 73 records from AMF colonization in Plantago. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 812 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 154 records from Shannon Index and species richness for arthropods. 1 records from Red list project inventory, bryophytes. 3 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4762866 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2420 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 8581 records from PlutoF platform observations. 26313 records from Herbarium Senckenbergianum (GLM) - Lichenes. 48731 records from SPSF - Herbário Dom Bento José Pickel. 2562 records from Inventario de la vegetación acuática vascular de cuatro regiones hidrológicas prioritarias del centro de México. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 30 records from Type Specimen Database of Museum and Institute of Zoology PAS. 24283 records from SANT-Algae. 145016 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 1117757 records from PRECIS. 29 records from Genetic variation of the 30 beech stands across three exploratories. 360279 records from Herbario Nacional Colombiano (COL). 7 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 188 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 1201 records from Monocotyledonous Geophytes of Fergana Valley. 59795 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 28 records from SMNS Palaeontological collection - Amber and fossil insects. 8 records from Naturalis Biodiversity Center (NL) - Pisces. 1910 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 5600 records from Flora del municipio de Culiacán, Sinaloa. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 12470 records from EPA River Biologists data. 5506 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 2250 records from UTEP Plants (Arctos). 149 records from Paläontologie Marburg. 323 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 1791 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163153 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 70911 records from SPF - Herbário da Universidade de São Paulo. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 70772 records from SANT Herbarium vascular plants collection. 2332 records from Collection du Musée d'Histoire Naturelle de Nice. 2 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 9349 records from Harriet Irving Botanical Gardens (HIBG). 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 17508 records from Species plots from the Norwegian Vegetation Mapping Programme. 616 records from Collection of botanical drawings by Georg Schweinfurth at B. 1 records from Fiocruz/CCFF - Coleção de Culturas de Fungos Filamentosos. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 267 records from MCME UPLB Museum Plant Collection. 48835 records from UFP - Herbário UFP - Geraldo Mariz. 10 records from Insect Collection from New Caledonia. 1705 records from University of Amsterdam (NL) - Páramo pollen reference collection. 61 records from Registros restauración ecológica- Magdalena medio. 558 records from NPL collections. 19100 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 99 records from French national collection of Solanum tuberosum. 107359 records from Colección Herbario Federico Medem Bogotá - FMB. 1459 records from Local BioBlitz Challenge 2013. 18273 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 220 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 1100 records from Taxonomía de los pinos del noreste de México. 4825 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 1092553 records from FLORIVON. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 37 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2620 records from Macroalgas marinas de la Región de Zihuatanejo, Gro.. 129 records from Conocimiento y conservación de las mamilarias endémicas del Valle de Tehuacán-Cuicatlán. 2213309 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1329 records from API_CRSN_Data. 7671 records from HERBAM - Herbário da Amazônia Meridional. 23004 records from Herbario Pontificia Universidad Javeriana. 112658 records from ICN - Herbário do Instituto de Ciências Naturais. 13 records from Meiobenthos of target sites of Crimea in 2009/2010. 2467 records from Proyecto interno ejecutado por la CONABIO: Los manglares de México: estado actual y establecimiento de un programa de monitoreo a largo plazo: 2a y 3era etapas. 68837 records from IICT Herbário LISC. 51110 records from Karplanter i vernet barskog og edelløvskog. 85002 records from Herbario Universidad de Antioquia (HUA). 10 records from Lund Museum of Zoology - Insect collections (MZLU). 5131 records from URM - Herbário Pe. Camille Torrand. 2435 records from Inventario Español de Especies Terrestres (MAGRAMA). 17 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 84077 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 13 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 346641 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 103307 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 13654 records from Árboles de Chiapas: registro georreferenciado de los ejemplares depositados en el herbario de la Academia de Ciencias de California (CAS). 642 records from Flora ficológica de la huasteca potosina. 44 records from Solanum_baretiae. 7475 records from BioGIS - Vascular plants - Israeli Gene Bank. 1 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 3257 records from fundiv france database. 10065 records from Malezas introducidas en México. 236 records from Abundanz_Infloreszenzenschlupf_Subplotebene_2008. 8937 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4943 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 127 records from Entomology, Natural History Museum, University of Oslo. 3809407 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 254 records from Inventario de Plantas Mámbita. 8589 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 35828 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 2 records from Eocene lantern fruits from Gondwanan Patagonia and the early origins of Solanaceae. 30 records from Hosted Invertebrate Collection 01. 1489 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 374 records from published_chenopodium_vulvaria_observations. 1 records from Inventario de las especies de hongos microscópicos en el Valle de Zapotitlán, estado de Puebla. 483 records from Inventory of Dogo-Kétou forest (South-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 6 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán. 5 records from IMOS - AusCPR: Phytoplankton Abundance. 119220 records from The digitization of plant specimens of NTU. 603 records from Oat French National Collection. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1735581 records from SA Flora (BDBSA). 8881 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 314 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 50106 records from Local Wildlife Site Surveys Berkshire. 8 records from Galls on Beech Trees in Hainich, 2008. 3 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 2 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 1071 records from NINA Vanndata øvrige arter. 40 records from AM: Freshwater Invertebrates (1900-2005). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 67236 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 71 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 219532 records from Phytochorologie des départements français. 2 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 4758 records from SMDB - Santa Maria Departamento de Biologia. 432 records from Estudio monográfico del género Echinopepon Naud. (Cucurbitaceae) en México. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 179970 records from BioFokus. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 219580 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 326 records from Culture Collection of Cryophilic Algae. 7187 records from Estudio florístico, ecológico y etnobotánico, en el área natural protegida "Tenancingo-Malinalco-Zumpahuacan", Estado de México. 585 records from Caracterización y monitoreo de la condición arrecifal en cinco áreas naturales protegidas y un área de influencia de Quintana Roo, México: Primera etapa. 306 records from Clare Biological Records Centre dataset. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 2344 records from Species composition of protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of JRS Biodiversity Foundation project. 256 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1 records from University of Florida Vertebrate Paleontology. 184 records from Bioblitz 2013 Copenhagen Denmark. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 16 records from Colección de microorganismos del CINVESTAV-IPN Fase I, Base de datos, Parte Vista Usuarios Internos. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 75686 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1343 records from Análisis de viabilidad para poblaciones de la cactácea amenazada Ariocarpus trigonus. 1423 records from Algas coralinas articuladas (Rhodophyta-corallinales) de México. 1881 records from Monitoring data from the federal state Bavaria (Germany). 153656 records from Museu Paraense Emilio Goeldi Herbarium. 4 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 6312 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 85 records from Macroalgas marinas de Baja California Sur Parte I: Bahía de la Paz y Bahía de la Ventana. 31 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 953 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 12005 records from Inventario florístico de la familia Boraginaceae en México. Fase II. 8735 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 52449 records from CESJ - Herbário Leopoldo Krieger. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 13716 records from OUPR - Herbário "Professor José Badini". 45 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 192948 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 892 records from Base de datos de la familia Fagaceae en el estado de Hidalgo. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 14520 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 726 records from HAS-Algae - Coleção Ficológica do HAS. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 6103 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 48 records from Ectomycorrhiza species on all VIP´s April 2008. 5441 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 868 records from Kartlegging av spredning av fremmede bartrær. 15866 records from HAMAB - Herbário Amapaense. 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 8366 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 1828 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 32 records from CUMV Fish Collection (Arctos). 6065 records from LISU Herbario Angola. 1385 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 1860 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 352666 records from Plantae of Costa Rica (INBio). 30818 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 5967 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 535 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 2385 records from MATRIX project, Mabira in Uganda. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 787273 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 620 records from Digitalización de la colección FITO-UBIPRO, de las enfermedades y sus agentes causales, de los cultivos agrícolas de la región centro de México. 77 records from Inhaltsstoffe_Blattmischproben_2008. 1 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 6000762 records from Artdata. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 414 records from Jardín Botánico Carlos Thays. Colección de Nativas Vivas. 299 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 13284 records from Herbier du Bénin. 15 records from Clasificación de tres especies endémicas de Mammillaria dentro del PROY-NOM-ECOL-059-2000. 76 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 9093 records from Flora of Słowiński National Park, Poland. 1843 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 1 records from Museum Victoria provider for OZCAM. 157 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 2883 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 78989 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 45 records from Vertebrados terrestres de San Juan de Camarones, Durango. 119 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 12678 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb).. 12062 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 17702 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 1292 records from Census of tapia forest plant species in central highland of Madagascar. 1802 records from Flora of tanzania. 2966 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 274860 records from MBM - Herbário do Museu Botânico Municipal. 777 records from INRA-Versailles Arabidopsis natural variants. 2 records from Ohio University Invertebrate Paleontology Collection. 13807 records from Flora de las playas y dunas costeras de México. 372 records from Algae (KBRC-AG). 49 records from The "Martian" flora: new collections of vascular plants, lichens, fungi, algae, and cyanobacteria from the Mars Desert Research Station, Utah. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 2243 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 307 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 238200 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 10895 records from Stabbetorp - Floristiske registreringer 2016. 527 records from Inventaire floristique de Beza Mahafaly. 8608 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 14 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 3404 records from Lista florística de la Costa Grande del estado de Guerrero. 625 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 2865 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 1 records from Insecta of Costa Rica (INBio). 17 records from Sarcinoid green algae (Chlorophyta) of Algal Collection of Soil Science Institute (ACSSI). 258 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 5 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 8950 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 906 records from Digital Florula - Las Cruces Biological Station. 24121 records from Endemic plants of the Congo basin. 2032 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 1 records from SDSM Botany and Paleobotany Collections. 3 records from Chrysomelidae of the Carpathians. 934 records from GenLink - Collected plant samples on grassland EPs. 138144 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 5366 records from Algae (S). 51 records from Araneae Collection. 19736 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 644 records from NCC Berkshire Chalk Grassland Survey 1985. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 145218 records from OHN. 5019 records from Algas marinas bentónicas de la Península de Yucatán y uso potencial de especies selectas. 429 records from TPWD HARC Texas Coastal Fisheries, Corpus Christi Bay Gill Net. 16 records from Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist. 11 records from Lund Museum of Zoology (MZLU). 618754 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 368864 records from Données ONF Faune-Flore-Fonge. 1516 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 6537 records from FCAB - Herbário Friburguense. 26614 records from Herbier de Nouvelle-Calédonie. 1 records from CAS Invertebrate Zoology (IZ). 103 records from Archives of the Arctic Seas Zooplankton. 997 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 1029 records from Freshwater plants of Cameroon. 490 records from flower availability 2007 Schwäbische Alb. 29624 records from Tallinn Botanic Garden. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 20 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 9 records from Chenopodium vulvaria. 11187 records from Herbarium areqvipense (HUSA). 1847 records from NCSM PaleoBotany Collection. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo en Nuevo León. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 857 records from Culture Collection of Algae. 6 records from Invert Paleo Specimens. 388 records from Algae, Norwegian College of Fishery Science. 31 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1401 records from Plant observations from Białowieża National Park. 20797 records from Norwegian Biodiversity Information Centre - Other datasets. 144 records from Checklist of Fabaceae Lindley in Balaghat Ranges of Maharashtra, India. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 4 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 90 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6131 records from Evaluation de la dynamique des espèces envahissantes (Pistia stratioides et Eichhornia crassipes) et de la flore aquatique au Bénin en association avec ces espèces envahissantes. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 2097 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 631 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 583 records from Invasive plant species recorded in protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones of Benin. Data mobilized in the framework of BID Regional project BID-AF2015-0066-REG and funded by EU. 160 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 852 records from flower availability 2008 Hainich. 932 records from Sistematización de la Colección de Algas Marinas del Centro Interdisciplinario de Ciencias Marinas CICIMAR-IPN. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 63874 records from La familia Asteraceae en México. Fase VI. 35 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 3288 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 66 records from Museum of Comparative Zoology, Harvard University. 621 records from BRFC Black Rock Forest Consortium Herbarium. 12537 records from Herbarium of the Université Libre de Bruxelles. 8078 records from tef-database. 3 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 126 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4969184 records from Australia's Virtual Herbarium. 1667138 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 36549 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 431 records from Plantas Bosque Seco Chicamocha. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 38468 records from Herbier de Strasbourg. 1 records from Flora of Suriname, volume VI, part I. 49 records from Interacciones en el dosel de la selva húmeda tropical e implementación de un sistema de estudio en este ambiente. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 23078 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 814 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 4059 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 197850 records from Vascular Plant Herbarium, UiB. 30 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 24 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 42530 records from Kathryn Kalmbach Herbarium. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 15 records from Chenopodium. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 154344 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 200887 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 496 records from Colección Limnológica Universidad de Antioquia. 216 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 21981 records from Natural History Museum Maastricht (NL) - Herbarium. 2 records from Naturalis Biodiversity Center (NL) - Collembola. 3 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1910665 records from Consortium of California Herbaria. 633 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 169 records from The Pteridaceae family diversity in Togo. 1993 records from Distribución, estructura poblacional y utilización del saguaro (Carnegiea gigantea (Engelm.) Britt. & Rose) en México. 98 records from Colección Nacional de Heliconias. 761 records from Monitoring data from the federal state Hesse (Germany). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 25 records from Revision of the Malagasy species of Homalium sect. Eumyriantheia Warb. (Salicaceae). 424602 records from iNaturalist Research-grade Observations. 807 records from Reunion_Coffea. 409 records from Herbario MAIA, colección de Quercus del INIA-CIFOR. 20146 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 806 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 163 records from Barcode de Bambúes nativos de México. 18894 records from UCBG TAPIR Provider. 1051 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 4858 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3669 records from ARKO strandeng. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 16 records from Dorset SW Pilot species dataset. 24143 records from Seasearch Marine Surveys in England. 171047 records from CONN. 35836 records from HUCS - Herbário da Universidade de Caxias do Sul. 17246 records from BioGIS - Vascular plants - HUJ Herbarium. 1075 records from Bryopyhtes in forest indices and traits. 3753 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 1972 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 50880 records from H.A. Stephens Herbarium. 3 records from Upper Silesian Museum, Bird Observations. 157 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 1585 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 368 records from Ecología poblacional de Abies hickelii en el Pico de Orizaba, Veracruz. 13615 records from Merseyside BioBank Active Naturalists (unverified). 701 records from El género Festuca (Poaceae: Pooideae) en México. 80 records from Eggplant French national collection. 5 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 18247 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 7556 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 4498 records from Flora of Japan Specimen Database. 6726 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 9259 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forèts sacrées des départements de l'Ouémé-Plateau et le Collines. Données mobilisées dans le cadre du projet JRS Bénin. 21736 records from University of Lethbridge Herbarium (LEA). 203 records from Invertebrates Collection of the Swedish Museum of Natural History. 258 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 3 records from Fungi Collection. 209207 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 9 records from Alien Species in Poland - Animals. 17 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 6 records from SAEON: Historical Research Survey Database (1897-1949). 106719 records from Estonian Museum of Natural History. 30 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 5681 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 4745 records from Collection botanique Le Grand A. (BOUM). 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 1752 records from Herbier National de Mauritanie (HNM). 2355 records from Estudio para una propuesta de plan de manejo de la palma chit (Thrinax radiata), en el Área de Protección de Flora y Fauna Yum-Balam. 43374 records from University of California Museum of Paleontology. 7605 records from NINA botanical collection. 516 records from Phytoplankton from the White Sea, Barents Sea, Norwegian Sea and Arctic Basin 1993-2003. 1914 records from Macrophytes_CLF. 419480 records from Meadow and Pasture Inventory (SJV). 370 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 1901 records from Flora acuática vascular del estado de Morelos, México. 7045 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 962 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 84303 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 5812 records from Las monocotiledóneas mexicanas, una sinopsis florística. 81 records from Aprovechamiento de venado cola blanca (Odocoileus virginianus) como estrategia para conservar áreas forestadas en la zona maya: Reserva Ría Lagartos, Yucatán. 981 records from Herbier du muséum Henri-Lecoq de Clermont-Ferrand . 211 records from KUBI Vertebrate Paleontology Collection. 98230 records from ALCB - Herbário Alexandre Leal Costa. 800 records from Reevaluación taxonómica de las especies de algas coralinas (Corallinales; Rhodophyta) que forman mantos de rodolitos en el Golfo de California, México. 6233 records from HUSC - Herbário Unisanta. 197107 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 8814 records from HPBR - Herbário Padre Balduino Rambo. 119367 records from Estonian University of Life Sciences. 106 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 40 records from Countryside Council for Wales - Shad Monitoring data. 1 records from CAS Ichthyology (ICH). 854 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 663 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 1855 records from corrego_fazendinha-gallery-forest_v2. 8436 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 601 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 8 records from Records of Wenchengia (Lamiaceae) from Vietnam. 13460 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 899 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 761 records from Dorset Heath - NBN South West Pilot Project Case Studies. 4963 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 39700 records from BioGIS - Vascular plants - A. Danin's point database. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 119 records from Dinámica poblacional de cactáceas amenazadas. 188 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 805 records from Monitoring data from the federal state Saxony (Germany). 6 records from Canada_BasinMegabenthos2002. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 582 records from tree climbing bryophytes & lichens at tree base and crown with traits. 248 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 19409 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Birdrace_Schräge_Vögel-Herford. 4 records from Birdrace-Die_Nachtraben-Stuttgart. 22 records from Im Bauerngarten. 123 records from VFD-H: Rheingau: Pferdeweide Loock. 122 records from Klasse 3a. 123 records from Seewasen. 68 records from Siegen/ Gymnasium Am Löhrtor. 23 records from Borkhart. 220 records from Küstenschutzwald. 142 records from FNL e.V.. 3 records from Spechtwald. 202 records from Kremmer Luch. 171 records from Beweidungsprojekt an der Nesse. 113 records from Flora. 34 records from Feriendorf Ober-Seemen. 50801 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 22 records from Förderzentrum Schmölln. 75 records from Kloster Eberbach. 92 records from LauWi. 99 records from Ehmkendorf. 50 records from Grenzturm Hohen Neuendorf. 34 records from Lech 2001. 151 records from Isarufer. 31 records from Fledermaus. 32 records from Waldsee. 28 records from Feriendorf des Kreises Gedern (Ober-Seemen). 88 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 153 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 113 records from Hochschulgelände (Bremen). 76 records from Biotop "Kohlbeke" (Berlin-Marzahn). 36 records from Heidesee / Halle. 41 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 5020 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 29 records from Berlin - Treptower Park / Karpfenteich. 41 records from "Schlechteberg" Ebersbach/Sa.. 41 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 65 records from Fuchsloch (Mohlsdorf/Ostthüringen). 67 records from Naturgrundstück (Eutin). 28 records from Lassentiner Moor (Niepars). 142 records from Kiesgruben Wemb. 9 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 98 records from Truppenübungsplatz Panzerkaserne Böblingen. 60 records from Schulgarten mit Klasse 8a (Essen). 96 records from Döchtbühlwald (Bad Waldsee). 40 records from Roter Berg Werdau (Leubnitz). 43 records from Waldhusener Moor (Lübeck-Kücknitz). 121 records from Föhrenried (Fronreute und Baindt). 15 records from AKG-Bensheim. 147 records from Artenvielfalt Kreis Gießen. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 34 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 164 records from Regenrückhaltebecken (Zeulenroda). 22 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 192 records from Deponie Klausdorf. 12 records from Alter Nördlicher Friedhof (München). 20 records from Motzener Tonsee. 136 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 68 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 75 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 94 records from Zielbach (Töll). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 50 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 215 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 16 records from Südpark (Bochum-Wattenscheid). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 34 records from Flusswerder in der Weser (Hameln). 60 records from Wedeler Au. 132 records from Bodenseeufer Radolfzell. 41 records from Zitadelle Berlin-Spandau (7b). 34 records from Kabelskebach (Kabelsketal, Saalkreis). 79 records from Steinbruch Mainz-Weisenau. 106 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 212 records from Triebesbach (Zeulenroda-Triebes). 44 records from Wiese am Unterbecken. 65 records from Ortelsbruch - Hangmoor bei Morbach. 13 records from Dellwiger Bach (Dortmund). 29 records from verschiedene Kleingewässer um Oldenburg/Holstein. 40 records from "Schwarzes Teich" (Waldpark Radebeul). 79 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 66 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 24 records from Örtzemündung (Stedden). 15 records from Hainbachtal in Oelsnitz/V.. 193 records from Wangerooge. 6 records from Kita-Wäldchen Fuchsturmweg Jena. 130 records from Umgebung der Grundschule Oderberg. 94 records from Naturhausgarten. 43 records from Die Wuhle. 101 records from Steinbruch Mainz-Weisenau, 2. Jahr. 24108 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 75 records from Wirbach. 191 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 97 records from Paul-Gerhardt-Schule Dassel. 145 records from privater Garten. 143 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 51 records from Alter Kreidebruch Saßnitz/Rügen. 90 records from Schussenaue bei Berg. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 59 records from Rund um das LUGY. 234 records from Ried und Sand - Artenvielfalt durch Beweidung. 24 records from Nationalpark Harz Schul-AG Braunlage. 23 records from Junge Heide, Radebeul/Dresden. 44 records from Insektenvielfalt Ahe/Weichelsee. 58 records from Schulgarten Hans-Carossa-Oberschule. 41 records from Ludwigshofen. 66 records from Landschaftsschutzgebiet Buchhorst 3. 86 records from Stever. 45 records from Bolzplatz. 259 records from Thistle Heads and Ermerged Insects. 14 records from Spielwiese. 6 records from Kindergarten. 65 records from Wassermann. 9 records from Willersalpe. 52 records from GymnQuerfurt. 27 records from Erft in Selikum (Neuss). 79 records from Landschaftsschutzgebiet "Holmer Sandberge". 33 records from Varnhalt. 18 records from Mittelstreifen. 67 records from Mainufer. 46 records from Rund ums Ökohaus (Würzburg). 19 records from Schulhof Sandhofenschule (Mannheim). 105 records from Brander Wald (Stolberg). 50 records from Wiesenbiotop am Wasserturm. 54 records from Balkon (Norderstedt). 76 records from Spießwoogtal / Königsbruch (Fischbach). 111 records from Artenvielfalt im Beckerbruch (Dessau). 8 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 37 records from Wasserwerkspark (Chemnitz). 69 records from Düne am Ulvenberg (Darmstadt). 28 records from Sandgrube Zaisertshofen. 91 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 77 records from Ökologischer Weinberg (Guntersblum). 16 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 39 records from Schwanseepark (87645 Schwangau). 78 records from Wirbach-Taubental (Bad Blankenburg). 36 records from Trockenrasen bei Dörndorf. 16 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 70 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 35 records from Urwald 3 (Bad Waldsee). 53 records from Trockenrasen Franzigmark (Halle/Saale). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 25 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 34 records from Wiese und Bach beim Unterbecken (Markersbach). 40 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 241 records from Garten J. Scherrer (Lachen-Speyerdorf). 45 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 9 records from Schutzgebiet Ochtersum. 36 records from Tag der Artenvielfalt BUND Kaiserslautern. 103 records from Außengelände KITA "Mäuseburg" Waldkirchen. 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 22 records from Heilpflanzen im Hainbachtal. 131 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 60 records from Dorfrand Mauderode. 110 records from Obstwiese Osterberg. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 16 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 125 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 31 records from Artensuche auf den Elbwiesen in Radebeul. 56 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 27 records from Umgebung des Spalatin Gymnasium Altenburg. 98 records from Warnowtal (Rostock). 30 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 4 records from Goethe-Hauptschule/Projekt I-10. 96 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 85 records from Selztal bei Friesenheim. 89 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 296 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 84 records from Naturschutzgebiet Lochbusch-Königswiesen. 20 records from Uferzone Wipper (Biesenrode). 19 records from Breitkopfbecken (Berlin-Reinickendorf). 53 records from NSG Leist bei Ziegenhain. 30 records from Flächennaturdenkmal Grubditz. 44 records from Amtsrain Apolda-Zottelstedt. 150 records from Gieselbachtal Fulda-Harmerz. 43 records from Artenvielfalt auf der Wiese. 34 records from Saalewiesen Naumburg. 38 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 35 records from Flora und Fauna am Mittelrheintal. 151 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 45 records from Schafsweide Seniorenhaus Berghof. 140 records from WildesMoor bei Schwabstedt. 95 records from Vielfalt verschiedener Wiesen. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 53 records from Weidegut Rechab. 123 records from Binsenwiesen. 79 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 155 records from Bammentaler Duft- und Heilkräutergarten. 87 records from Grillhütte Wettsaasen, Wiese, Hecken. 46 records from Isartal Dingolfing. 120 records from NABU-Auerochsenweide. 53 records from Weidewirtschaft. 56 records from Birkenloh. 34 records from Kochertgraben II. 61 records from Dalbekschlucht. 51 records from Höltigbaum. 47 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 71 records from VFD-RP: Taunus: Ponykoppel Thurner. 112 records from Waldstück Bremerhagen LK Bio Kl. 12. 63 records from Hochschule Zittau/Görlitz. 74 records from Rund ums Cani. 35 records from GE-Brühl. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 106 records from vegoek. 10 records from Neanderthal. 52 records from Naturerlebnisraum Koppelsberg (Plön). 1 records from Regenwasserabfangsbecken (Erlenbach). 16 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 87 records from Steinbruch Mainz-Weisenau, 3. Jahr. 84 records from Gelände des Schulzentrums am Himmelsbarg. 80 records from VFD-H: Heidenrod: Pferdeweide Mürth. 125 records from Biosphäre Bliesgau. 31 records from NABUGEO1. 10 records from Feuchtwiesen Wippertal bei Wippra. 9 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 6 records from Birdrace-Usedommeln-Ostvorpommern. 75 records from Leben im Finkensteiner Moor. 53 records from Wulfsmuehle/Pinnau. 30 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 39 records from Landschaftspark St.Leonhard-Deisendorf. 2 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 14 records from Zoo Frankfurt. 58 records from Industriebrache (Kempen). 4 records from Kurler Busch (Scharnhorst). 1 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 27 records from Schulgarten Fichteschule. 1 records from Schulgelände Kranich-Gymnasium (Salzgitter). 4 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 34 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 49 records from Kinderbauernhof Pinke-Panke. 32 records from LSG "Großes Bruch". 30 records from 8c. 1 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 1 records from Bach. 2 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 109 records from Römertal (Steinpleis). 35 records from Sternwiese Mülheim-Broich. 17 records from Naturerfahrung. 14 records from Steinbachtal (Würzburg). 29 records from Schulhof A.-Lindgren-Schule (Elmshorn). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 73 records from Klütwald. 23 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 30 records from Park Schönfeld (Kassel). 37 records from Schulhof Liebfrauenschule Oldenburg. 29 records from Garten in Schmölln. 21 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 51 records from Schrebergarten Düsseldorf Oberkassel. 26 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 22 records from Mittelriede Höhe Gliesmarode-Braunschweig. 48 records from Dörnberg. 6 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 15 records from Schulgelände Ceciliengymnasium. 4 records from Regenwasserabfangbecken. 1 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 20 records from Schafheide im Böblinger Wald. 23 records from Regenrückhaltebecken Bad Bevensen. 57 records from Naturschutzgebiet Kochertgraben. 28 records from Streuobstwiese Haus Zeitz. 21 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 34 records from Gym Freyung. 7 records from Erhard Sopp. 53 records from Hoher Stein Kallenhardt. 23 records from Mühlenbach bei Buxtehude. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 2 records from Tiere im Teichgebiet. 12 records from Bachabschnitt der Nette (Osnabrück). 5 records from Naturschutzgebiet Ahrschleife (Altenahr). 72 records from Draubiotop Lavamünd. 36 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 11 records from Waldgebiet Todtnau- Sonnhalde. 38 records from Schulgarten-St.-Georg-Gymnasium. 57 records from Mauervegetation,Flechten und anderes. 27 records from Estetal (Buxtehude). 14 records from Schulgarten der Hainbuchenschule (Hagenbach). 33 records from Issumer Fleuth. 8 records from Schulteich Heinrich-Mann-Schule. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 10 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 17 records from Zwickau- Schwanenteich. 29 records from Nationalpark Harz Juniorranger. 5 records from Schulgelände Lise Meitner Realschule (Paderborn). 382 records from Sudeniederung (Amt Neuhaus). 62 records from Streuobstwiese. 2 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 1 records from Glemstal (Leonberg). 2 records from Lerchenauer Baggersee (München). 23 records from Lahnufer in Villmar. 6 records from Kaisertal. 2 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 15 records from Kaltenkirchen Brache. 1 records from Mikroorganismen. 3 records from Tümpel Schulbiologiezentrum. 5 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 51 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 9 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 7 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 17 records from Salzwiese Diekskiel. 310 records from IBF Monitoring of Plant Galls. 13 records from FND "Weißer Berg" Leißling. 3 records from FFR Hausen. 39 records from Georgs-Padd (Wangerooge). 8 records from Warnowufer Groß Klein. 5 records from Im und um das Schulhaus. 1 records from LBV-Kindergruppen Markt Tussenhausen. 3 records from Wattuntersuchung (Cuxhaven). 2 records from Wattenmeer-Safari (Wurster Watt). 19 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 9 records from Kleinstbiotop mit Schulteich/Weißwasser. 5 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 13 records from Nachtaktiv im Ökogarten (Bad Waldsee). 4 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 23 records from Tiere und Pflanzen um uns herum !. 37 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 2 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 1 records from Kohlbach (Sulzfeld). 2 records from Tauchen und Meer. 1 records from Bachpatenschaft Beeke. 8 records from Ohemoor (Hamburg/Norderstedt). 2 records from Sächsische Schweiz (Wehlener Gebiet). 3 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 47 records from Landschaftsschutzgebiet Buchhorst 4. 33 records from Schulteich Freie Waldorfschule Darmstadt. 8 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 3 records from Stadtrandlandschaft Apolda-Nord. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 29 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Schulinnenhöfe (Gelsenkirchen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 54 records from Waldi-Weiher. 4 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 97 records from Tiere und Pflanzen am Pfannenbach. 1 records from Karpfenteich, Klasse 6d. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 206 records from FFH-Gebiet "Calwer Heckengäu". 71 records from Schulgelände Paul-Gerhardt-Schule. 44 records from Landschaftsschutzgebiet Schmutterwald. 54 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 624 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 206 records from Bannwald Burghauser Forst. 82 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 139 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 171 records from Rohrmeistereiplateau und angrenzendes Gebiet. 31 records from Fürstenberger Ralley Teil 3. 58 records from Müritz-Nationalpark. 60 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 218 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 282 records from Pöhlberg bei Annaberg. 58 records from Kaniswall/ Gosener Wiesen an der Spree. 129 records from Expedition "Schulgelände". 584 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 64 records from Haarbach Höfe. 308 records from Schulzentrum "Parc Hosingen". 80 records from LK 11 im Mönchspark. 49 records from Schulwald Grundschule Brügge. 136 records from Bernhardsthal. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 104 records from VFD-RP: Eifel: Orchideenweide Ankly. 223 records from Weinberg Reichersdorf. 78 records from Schulwald Marksuhl. 1 records from BIRDRACE Gätkes Erben. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 1 records from BIRDRACE Guckers Offenbach. 1 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from BIRDRACE Unterste Niederrhein-Rennvögel. 60081 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2 records from BIRDRACE Immerwiederhopf. 165 records from Naturschutzgebiet Börstig bei Hallstadt. 200 records from Tag der Artenvielfalt in Heidelberg. 31 records from Wiesen am Treffpunkt Freizeit. 45 records from Tongrube bei Hettstedt. 18 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 42 records from FFH-Gebiet Klosterwasser/Burkau. 60 records from Gronau - auf der Suche nach dem Neunauge. 44 records from Langes Tannen(LMS), Klasse 5d. 19 records from Liether Park 2 (LMS), Klasse 6c. 272 records from Schatzinsel Wangerooge. 130 records from Lustbach-Umland. 32 records from Königsdorfer Wald. 61 records from VFD-HH/SH: Pferdweide Lammert. 101 records from Owere Fiddel. 65 records from NSG Forst Zinna-Jüterbog-Keilberg. 44 records from Hettstadt Gehäge. 96 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 337 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 75 records from Tornoer Teich. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 53 records from Biotope im Schulumfeld. 50 records from Streuobstwiese Stedar. 63 records from Liether Kalkgrube. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 111 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 36 records from Lebensraum Dorf. 203 records from Schulgarten der Volksschule. 83 records from Sürther Aue. 80 records from Feldweg Waldkirchen. 90 records from Aachtobel. 123 records from Bodenteicher Seewiesen. 209 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 43 records from Wälder im Hainbachtal. 78 records from Steinbruch Kronungen. 47 records from Ober-Olmer Wald. 55 records from Rund um den Hainbergsee. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 68 records from "Ahrschleife bei Altenahr". 171 records from Pflanzen und Tiere im Burgwald. 33 records from Wir erkunden die Hofau, Klasse 5c. 18 records from Waldwiese. 11 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 44 records from Von der Nutzung zur Natur. 49 records from VFD-H.: Rheingau: Bärstadt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 23 records from Liether Park 1 (LMS), Klasse 5b. 2 records from A synoptic revision of the Malagasy endemic genus Socratina Balle (Loranthaceae). Candollea 69: 65 - 73. In English, English and French abstracts.. 1 records from BIRDRACE Die Schwenker-Birder. 10 records from Landschaftsschutzgebiet Buchhorst2. 1 records from Schulgarten Waldorfschule Hassfurt. 22 records from Unter hellen Zinnen und finsteren Grotten. 26 records from FFH-Gebiet Paartal. 8 records from Schulgarten Janusz-Korczak-Realschule. 25 records from Geführte Wanderung im Eselsbachtal. 16280 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 8 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 32 records from Wahner Heide LK 12 Biologie. 42 records from Aktion der Klasse H2 in Simmelsberg. 84 records from VFD HH/SH "Pferdeweide Lemsahl". 29 records from Schüler erforschen die Helme-Aue. 5749 records from NX - Herbário Nova Xavantina. 32 records from Rosarium (LMS), Klasse 6a. 7 records from Leben auf einer Sturmfläche. 25 records from Reusaer Wald. 37 records from Rechts des Inn Höhe Hofau Rosenheim. 29 records from Schulgarten Zinnowwald-GS. 97 records from Evaluación de las categorías de protección de la familia Iridaceae. 11 records from Feuchtwiese Grüne Mitte, Klasse 5a. 74 records from Teich im Wald zwischen Böblingen und Schönaich. 16 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 9 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 9 records from Riekdahler Wiesen. 13 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 17 records from Höhle am Neuweg / Sächsische Schweiz. 43 records from Kindervilla Außengelände. 4 records from Flora und Fauna am Mühlberg. 77 records from VFD-RP: Taunus: Mähweide Dehe. 124 records from "Schwarzwassertal" bei Pobershau. 1 records from Streuobstwiese Alt Necheln. 12066 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 2712301 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 15 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 2965 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 798 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 246 records from Seaweeds records from Argentina and Uruguay. 2 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 5 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 3 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 66 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 2 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 65 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 8555 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 2252 records from Hawaiian Algal Database. 7339 records from Base de datos de las pteridofitas del estado de Veracruz, México. 3810 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 10666 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 28 records from Chrysomelidae of Poland. 10 records from Biodiversity records from Ireland - general. 215 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 34 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 27 records from Diveboard - Scuba diving citizen science observations. 8 records from CM Vertebrate Paleontology Collection. 186849 records from Bryophyte herbarium, NTNU University Museum. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 7621 records from Bryophyte collection of Porto Herbarium (PO). 49781 records from Continuous Plankton Recorder Dataset (SAHFOS). 9 records from Ektomykorrhizen auf VIP Schorfheide (Wald). 250427 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 56 records from Illinois Natural History Survey Insect Collection. 565 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 1011 records from flower availability 2008 Alb-korrigiert. 25596 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 65459 records from OAC-BIO Herbarium. 93 records from Invasive Non-Native Species, Outer Hebrides. 69994 records from Bryophyte herbarium, Oslo (O). 25903 records from VIC - Herbário da Universidade Federal de Viçosa. 8420 records from Polish seed gene bank – historical passport data of accessions. 2421 records from Census of plant species in Toffo forest reserve. 1538 records from Diversidad de orquídeas en la región El Momón-Margaritas-Montebello, Chiapas, México. 846 records from Inventaire National du Patrimoine Naturel : CBN Méditerranéen de Porquerolles. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 117 records from (Appendix B) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1105-4. 1044 records from Naturalis Biodiversity Center (NL) - Diptera. 30 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 54400 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 310 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 21 records from Distribution of palynomorphs in surface sediments of the Laptev Sea. 114 records from Spores and dinoflagellates of Site 175-1075. 100 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 22 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 88 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Phytoplankton counted in three surface sediment samples from the South Atlantic at station PS2230-1, PS2367-1 and PS2376-2. 258 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 55228 records from Herbario de la Universidad de Granada: GDA. 41 records from (Table 2) Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/2 and M34/2. 12 records from Dinoflagellate cysts of mooring MST-8 (station 905), full and empty cysts. 23 records from Dinoflagellate cysts of mooring MST-9 (station 915), full and empty cysts. 1 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 32 records from Dinoflagellate cyst counts on sediment core ABC26. 205 records from Dinoflagellate cyst countings of sediment core MD95-2002. 131 records from Dinoflagellate cysts counts of sediment core MD95-2010. 222 records from Dinoflagellate cysts counts of sediment core MD95-2042. 688897 records from naturgucker. 542 records from Evaluación genética y demográfica de Agave victoriae-reginae T. Moore y aplicación del cultivo de tejidos para su conservación. 14108 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 8 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 154 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 46 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 90 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 43 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 25451 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 11 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 2994 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 17 records from NCC Berkshire Rare Plant Surveys 1985-1987. 3 records from Fungi and Lichens, Outer Hebrides. 864 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 4 records from Phytoplankton abundance in surface water during cruise CD60. 37 records from Phytoplankton abundance in surface water during cruise CD61. 1 records from Phytoplankton abundance at station CD46_1005C#4. 1 records from Phytoplankton abundance at station CD46_1305C#2. 1 records from Phytoplankton abundance at station CD46_2005C#4. 3 records from Phytoplankton abundance at station CD47_0306C#7. 5 records from Phytoplankton abundance at station CD47_0606C#7. 1 records from Phytoplankton abundance at station CD47_0906C#6. 4 records from Phytoplankton abundance at station CD47_1206C#7. 1 records from Phytoplankton abundance at station CD47_2805C#5. 1 records from Phytoplankton abundance at station CD47_3105C#4. 1 records from Phytoplankton abundance at station DI182_11864#61. 1 records from Phytoplankton abundance at station DI183_11872#3. 3839 records from Dataset of Global Change, altitudinal range shift and colonization of degraded habitats in mediterranean mountains (MIGRAME). 25 records from Erik Acharius lichen collection. 2493 records from flower visitor interactions 2008. 19 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 45 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1768-8. 54 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 7421 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 43 records from Dinoflagellate cyst counts of sediment core GIK23071-3. 430 records from IASTracker. Invasive Alien Species database. 2203 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Actuopalynology National Collection (BAPa).. 61 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 817 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 1 records from Lice (Phthiraptera) of Ireland. 9 records from Vigna pandeyana (Fabaceae), a new species from northern Western Ghats, India. 4129 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 82 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia.. 7886 records from English Nature Oxfordshire Chalk Grassland Survey. 10337 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 284 records from Botanical collection of the National Museum. 155 records from The Distribution Atlas of Butterflies in Poland. 4851 records from National Trust - Hatfield Forest species data held by The National Trust.. 80273 records from Scottish Natural Heritage - Standing Waters Database. 3161 records from Census in Agrimey forest reserve (southern Benin). 22876 records from Field Museum of Natural History (Geology) Paleobotany Collection. 7122 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 1840 records from English Nature Oxford City Surveys. 9 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 5 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 9422 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 5169 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 6584 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 11185 records from Registros biológicos del género Piper en el herbario HUA. 12 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 103 records from Scottish river macro-invertebrate records from 2007 collected by SEPA. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 1910 records from UTEX Culture Collection of Algae at The University of Texas Living Algae Holdings. 307 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 39 records from Benthos counted on dredged samples during Valdivia cruise VA44. 77 records from Benthos counted on dredged samples during Valdivia cruise VA53. 485 records from Freiburger GEO-Tag der Artenvielfalt. 10 records from Sandloch - Höhle. 596 records from Biosphärenpark Wienerwald - Pfaffstätten. 206 records from Kühmark bei Wetzlar. 177 records from Eschlberg Thalhausen. 527 records from GEO-Hauptveranstaltung in "Wildtierland". 71 records from Sahrbachtal Kreis Ahrweiler. 73 records from Schulgelände des Schulzentrums am Himmelsbarg. 125 records from Baggerseen bei Krauchenwies. 21 records from Schulaktion des Dienzenhofer-Gymnasiums. 30 records from Schriesheimer Steinbruch. 29 records from Artenvielfalt in der Kinderakademie im RFZ. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2 records from Die Bachspezies 2008/2009. 25 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 3 records from Ökosysteme rund um Wedel. 101 records from Mangfalltal. 4 records from "Am Riedert" im Westerzgebirge. 2 records from Wälder und Seen rund um den Mühlenberg. 30 records from GEO-Tag am Hohlen Stein. 510 records from LBV 100 - Artenvielfalt am Rothsee. 4 records from Grünanlagen Stadt Brandenburg an der Havel. 3 records from Zwischen Enz und Schule. 38 records from Naturpark Kottenforst-Ville 18.6.09. 88 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 218 records from Bayerische Donau - Leipheim. 62 records from Aktion - Friedensburg Oberschule. 28 records from Koleopterologen am Bausenberg. 147 records from Artenvielfalt im Rhein-Neckar-Raum. 6 records from Aktion des Romain-Rolland-Gymnasiums. 23 records from Artenvielfalt auf Zollverein. 330 records from Schatzinsel Norderney. 136 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 175 records from Biotope in Rheine - Aktion 350. 99 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 318 records from Schanzenanlage Bergham. 92 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 268 records from Dornwanger Moos. 70 records from Die Teiche im Britzer Garten. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 236 records from Butterberg, Dardesheim. 2 records from Kleinod unter Hochspannung. 5 records from Tuttlinger Tag der Artenvielfalt. 33 records from Naturpark Kottenforst-Ville 15.6.09. 30 records from Liether Park (LMS), 6g. 63 records from Nationalpark Jasmund. 390 records from Bulau. 190 records from Luderbusch. 83 records from Werl macht sich auf die Suche. 77 records from Schulgarten Zinnowwald-Grundschule. 5 records from Wiese. 5 records from Wanninchen. 5 records from Schulwald Regionale Schule Sprendlingen. 46 records from Rur. 377 records from Inventory of Niaouli forest (South-Benin). 36 records from Parkuntersuchung Weißer See. 26 records from Feuchtbiotop Weidenkaule. 1 records from Haselbachtal. 51 records from Mönchspark. 248 records from Wälder bei Nordkirchen. 68 records from BB-Biodiversität b. 251 records from Projekt Dellbrücker Heide. 1 records from Kirchenforst. 24 records from Naturpark Kottenforst-Ville 19.6.09. 56 records from Rund um die Sausenburg. 104 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 328 records from Bayerische Donau - Blindheim Donaubrücke. 50 records from Streuobstwiese Stedar 2008. 122 records from Schloss Fasanerie Eichenzell. 83 records from Donauinsel des BN bei Entau. 78 records from Streuobstwiese Stedar 2009. 25 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 44 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 19 records from Liether Park (LMS), 5a. 17 records from Liether Park (LMS), 6c. 23 records from Liether Park (LMS), 6b. 79 records from Schiller Gymnasium Hof 10b. 86 records from Schieferbrüche. 36 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 37 records from Reifrocknarzissenwiese Löcknitz. 34 records from Schulhofuntersuchung Thomas-Mann-OS. 35 records from Lebensraum Walram. 1 records from Wildnis Sturmschaden. 72 records from Artenvielfalt des "Grünen Klassenzimmers". 22 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1 records from Heckenstreifen am Zehntbergweg. 177 records from Naturpark Sternberger Seenland. 3 records from Trockenwiesen und angrenzender Waldrand im Hainbachtal. 2 records from Wie viel Natur gibt es im Park?. 26 records from Stadtwald Heide. 115 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 35 records from Listhof und Umgebung. 29 records from Naturpark Kottenforst-Ville 16.6.09. 35 records from Naturpark Kottenforst-Ville 17.6.09. 61 records from Raus in die Natur. 53 records from Rund ums Schulgelände. 19 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 147 records from Bayerische Donau - Neu Ulm. 25 records from NABU-Fläche am Bösselhausener Weg. 87 records from Exkursion Ebertsheimer/Grünstädter Berg. 86 records from Binsenwiesen im Bizzenbachtal. 91 records from Pfingstexkursion Alter Bessin. 107 records from Oberes Schindelbachtal. 76 records from Artenvielfalt vor unserer Kita-Haustür. 29 records from BB-Biodiversität a. 36 records from Seeufer ehem. BUGA-Gelände. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 29 records from Leben in den Elbwiesen. 22 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 42 records from Wiesen in der Grünen Mitte. 12 records from Bilder der Natur. 98 records from Artenvielfalt und Kulturlandschaft. 384 records from Naturschutzgebiet Lüneburger Heide. 51 records from Dalbek-Schlucht. 35 records from Aktion Wiese und Wegrain Gitzenheide. 47 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 1 records from FTEA. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 3412 records from Plant Specimens collections of the Kyushu UNniversity Museum. 48 records from MfN - Fossil invertebrates Ia. 174 records from MfN - Fossil invertebrates IIb. 17 records from MfN - Fossil invertebrates III. 102 records from MfN - Fossil vertebrates IV. 16100 records from MfN - Fossil plants (Cenophytic). 7713 records from MfN - Fossil plants (Mesophytic). 13080 records from MfN - Fossil plants (Paleophytic). 1 records from MfN - Fossil vertebrates II. 3 records from MfN - Fossil plants II. 1 records from Mammal Collection. 31 records from Fragment size of individual Fagus sylvatica trees based on microsatellite markers. 894 records from Red list project inventory, vascular plants. 180 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 4 records from Phytoplankton abundance at station DI182_11862#3. 1720 records from KTU Pinophyta. 15851 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 8853 records from Vascular Plants Collection of National Museum of Nature and Science. 334 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 16 records from (Table 1) Species abundance at DSDP Hole 63-467. 2382 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 20153 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 22709 records from UCT: South Africa Seaweeds(1905-2008). 11494146 records from Dutch Vegetation Database (LVD). 1 records from Biodiversidad microbiana de los ecosistemas marinos en la Isla Cayo Serrana durante la Expedición Seaflower 2016. 1148 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 44879 records from Bolus Herbarium Specimens Collection (1865-2009). 757817 records from Flora Atlas N.T.. 102 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 20998611 records from INPN - Données flore des CBN agrégées par la FCBN. 219 records from INERA-Luki reservation herbarium (CABIN project). 29 records from Diversidad genética en dos especies mezcaleras. 3728 records from Herbier de Wallis et Futuna. 11374 records from EFC - Herbário Escola de Florestas Curitiba. 35658 records from ASE - Herbário da Universidade Federal de Sergipe. 301 records from Modelación de la distribución geográfica de las especies del género Abies presentes en México. 163788 records from UEC - Herbário da Universidade Estadual de Campinas. 60 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 64 records from GenLink - Spatial coordinates of analysed Veronica chamaedrys individuals. 3 records from UWBM Herpetology Collection (Arctos). 12678 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1517406 records from NZ National Vegetation Survey occurrence data. 2394 records from Rådgivende Biologer. 920 records from BioBlitz Barcelona 2010-14. 52961 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from MSB Parasite Collection (Arctos). 3 records from Benthic macrofauna abundance of subcores of sediment core 13200-045. 41 records from Abundances of organic-walled dinoflagellate cysts in sediment core GeoB5546-2. 7 records from Northern Territory Museum and Art Gallery provider for OZCAM. 39 records from New records for Albania based on taxa from the Prespa National Park. 334 records from Listado florístico y etnobotánico de las plantas medicinales de los huicholes del río Chapalagana, Jalisco y del Nayar, Nayarit. 9 records from Bats of Poland. 72082 records from ICN - Universidad Nacional de Colombia. 25 records from Dinoflagellate cysts from sediment core PS1295-4. 66 records from Dinoflagellate cysts from sediment core PS2138-1. 3 records from Dinoflagellate cysts from sediment core PS2458-4. 19 records from Dinoflagellate cysts from sediment core PS2471-1. 36 records from Dinoflagellate cysts from sediment core PS2741-1. 9 records from Dinoflagellate cysts from sediment core PS2757-8. 17 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 3 records from (Table 4b) Calcareous nannofossil distribution on ODP Hole 117-721B. 2 records from (Table 6a) Calcareous nannofossil distribution on ODP Hole 117-731A. 420573 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1083 records from AlgaTerra. 59871 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 163247 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 4690 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 159226 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 9615 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 1100 records from Pinos del Noreste de México (UANL). 486 records from Colección de Flora Ficológica Marina de Tamaulipas, México (UANL). 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 38497 records from Herbario del CIBNOR. 33 records from The national database for marine data (MADS). 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 46003 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from Collection Crustacea NHCY. 332 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 4 records from Bayerische Donau - Etterzhausen. 61 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 10 records from Bayerische Donau - Riedlingen. 24579 records from Jardin botanique de Montréal (JBM). 14 records from Bayerische Donau - Tapfheim. 113 records from Artenvielfalt rund um die Dalbek-Schule. 48 records from Biosphärenreservat Mittelelbe. 1 records from Biotop Alexander-von-Humboldt-Schule. 996 records from Especies ornamentales invasoras: el caso de Kalanchoe delagoensis. 1 records from "Schule am Inselsee" Güstrow. 14 records from Exkursion in der Ehrbachklamm/ an den Erbach. 2 records from Familientag am Schorberg. 12 records from Feuchtbiotop Otto-Hahn-Gymnasium. 1 records from Der Kreuzenzian und sein Bläuling. 8 records from 2. Aspacher GEO-Tag der Artenvielfalt. 2 records from 2. Donauinsel bei Entau. 52 records from Fliegenhaupt Marksuhl. 70701 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 2540 records from Marchantiophyta / Hepatics / Liverworts of Russian Fennoscandia. 35 records from Flora und Fauna im Brexbachtal. 10 records from Fluss - Vielfalt. 56 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 119 records from Grünes Germersheim. 2 records from Grünfläche Forckenbeckplatz. 31 records from Kindervilla Aussengelände/ Hiltroper Park. 1 records from LUNG-Naturwiese. 175 records from Neißetal. 51 records from Ober-Olmer Wald 09. 1 records from Parthenaue. 7791 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 1 records from Regenwasserabfangbecken Erlenbach. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 10 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 54 records from Schulwald Sprendlingen. 10 records from Steinbruch Mainz-Weisenau, 4.Jahr. 75 records from Sukzession Industriebrache. 8 records from TBW-Schafberg. 2 records from Tauchaktion. 1 records from Vogelwelt im Europa-Rosarium. 9 records from Volkspark Prenzlauer Berg. 13 records from Wasser-Lernort Nettemündung. 3 records from Wasserbachsee. 43199 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 102148 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 45896 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 437 records from Gymnospermatatophytina Collection of Saitama Museum of Natural History. 2777 records from Bryophyta Collection of Saitama Museum of Natural History. 7644 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 2457 records from Amphibian and Reptile (NSMK-AR). 127 records from Marine Plants (NHMC-SA). 111 records from Fossil (WSHN-FO). 1000 records from Plant (KOBG_PL). 105 records from Fossil (NSMK-FO). 5516 records from Plant (KIWE-PL). 13611 records from Plant (JNHM-PL). 8 records from Birds (JNHM-BI). 1 records from Insect (HUNM-IN). 988 records from Plant (HBBG-PL). 3863 records from Plant (MNHM-PL). 289 records from Plant (SMNH-PL). 3790 records from Plant (NHMC-PL). 2366 records from Coimbra Collection of Algae. 7 records from Insect (JNHM-IN). 4 records from Insect (MNHM-IN). 1015 records from Alga (KIWE-AG). 3934 records from Plant (GFEI-PL). 354 records from Fossil (GNHM-FO). 83336 records from Plant (NSMK-PL). 983 records from Plant (NHMK-PL). 380 records from Fossil (MNHM-FO). 1984 records from Plant (JJHA-PL). 186 records from 녹조류 DB. 80105 records from Herbaria of the University and ETH Zürich. 2066 records from Bryophyte collection of Jyväskylä University Museum. 1260 records from Mongolian Plant (MMNH-PL). 10928 records from TRTE Herbarium (TRTE). 1 records from IZIKO South Africa Museum Collection (1800-2013). 609 records from Collection botanique Mulon L. (BOUM). 27828 records from svalbardflora.no. 110 records from South American Antarctic Marine Biodiversity Literature. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 1 records from Collection Polychaeta - ZIM Hamburg. 1 records from Collection Hydrozoa - ZSM München. 9 records from Collection Crustacea - ZMB. 12 records from Collection Vermes - ZMB. 96482 records from Tiroler Landesmuseum Ferdinandeum. 2624 records from The Fungal Collection at the Botanische Staatssammlung München. 25300 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 396476 records from IBF Monitoring of Vascular Plants. 1400 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 215 records from IBF Monitoring of Lichens. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 342 records from IBF Monitoring of Fungi. 1484 records from The Lichen Collection at the Botanische Staatssammlung München. 652 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 28 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 7737 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 29805 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 13 records from Landwehrbach. 7829 records from Universidad Autónoma de Madrid, Biología, Acalypha. 2077 records from Vascular plant specimens of Iida City Museum. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 65 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 78 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE255. 12 records from (Figure 6) Range chart of dinocysts of ODP Hole 104-642C. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE258. 23 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 16 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE241. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 44 records from (Figure 7) Range chart of selected dinocysts and acritarchs of ODP Hole 104-643A. 64 records from (Figure 6) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642C. 2548 records from Restauración experimental de un popal invadido por el zacate alemán (Echinochloa pyramidalis, POACEAE) en el sitio Ramsar No. 1336 La Mancha y El Llano. 71 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 1584 records from Marineplant (JBRI-SA). 4438601 records from Tropicos Specimen Data. 140 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 128 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 12 records from (Appendix A) Dinoflagellate cyst analysis of surface sediment samples off West Africa. 15 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 1 records from Coleoptera Collection. 81 records from (Table 2) Distribution of dinoflagellate cycst in OFP Hole 123-765C. 12 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE278. 1 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 31 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 9638 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 265 records from AIS Wildtype Populations of Arabidopsis. 471 records from flower availability 2008 Schorfheide. 12 records from (Table 3) Distribution chart of dinoflagellate cysts and acritarchs from DSDP Hole 27-263. 180 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 39 records from Dinoflagellate cyst species composition of recent surface samples (Appendix). 5 records from (Table 2) Median abundances of macrobenthos in surface sediments. 554120 records from BRERC species records recorded over 15 years ago. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3005 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 16 records from (Table 3) Distribution of dinoflagellate cysts in ODP Hole 103-641A. 102 records from EDIT - ATBI in Spreewald (Germany). 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 9 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 13 records from (Table 2) Eocene-Oligocene benthic foraminifers abundance in ODP Hole 124-767C. 23 records from SysTax - Zoological Collections. 32 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 32 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE275. 18 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 21 records from Palynomorph concentrations in ODP Hole 105-645B samples (Table 1). 11 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 14 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 1 records from Naturhistorisches Museum Mainz, Zoological Collection. 2372 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 7309 records from Botanical Research Intitute of Texas. 576292 records from Natural History Museum (London) Collection Specimens. 6 records from (Table 7) Dinoflagellate cyst species distribution in ODP Hole 112-680B. 7 records from (Table 6) Dinoflagellate cyst species distribution in ODP Hole 112-679D. 12 records from Chenopodieae. 11 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 64 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 110 records from Evaluación del estado de conservación, uso y amenazas de Yucca queretaroensis Piña (Agavaceae) y la pertinencia de incluirla en los Apéndices de la CITES. 7 records from (Table 8) Dinoflagellate cyst species distribution in ODP Hole 112-681B. 6 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 7 records from (Table 10) Dinoflagellate cyst species distribution in ODP Hole 112-686B. 7 records from (Table 11) Dinoflagellate cyst species distribution in ODP Hole 112-687B. 11 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2007. 9 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 9 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 14 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 105522 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 4268 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 4 records from Bumblebees, cuckoobees and butterflies in southern Poland. 1645 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 102 records from Clitellata - SMF. 75936 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 292322 records from Natural History Museum, Vienna - Herbarium W. 5291 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 3 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 862 records from Sistemática del género Polianthes L (Agavaceae). 168 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 3272 records from Flora útil del Municipio de la Huerta, Jalisco. 13449 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 2430 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 916 records from Revisión taxonómica del género Furcraea (Agavaceae) en México y Guatemala. 12908 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 1142 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 1006 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 7989 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1454 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 3638 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 4416 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 3458 records from Biodiversidad de Datura (Solanaceae) en México. 240 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 456 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 4148 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3014 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 34 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 2373 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 15852 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 14365 records from Lista florística preliminar de Tamaulipas. 3468 records from Flora de macroalgas del litoral oaxaqueño. 2688 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 2702 records from Pteridoflora de Morelos. 15006 records from La familia Asclepiadaceae en México. 1575 records from Inventario de la vegetación acuática vascular de la reserva de la biosfera Pantanos de Centla, Tabasco. 398 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 4568 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 2 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 502 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 1308 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 1774 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 8600 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 78 records from (Table T2) Dinoflagellate stratigraphy of ODP Hole 184-1148A. 3786 records from Las especies endémicas de plantas en el estado de Jalisco, su distribución y conservación. 2612 records from Flora genérica de las gramíneas del estado de Tlaxcala. 52 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 3200 records from Florística de la reserva de la biósfera de Mapimí. 1130 records from Flora vascular del cerro El Zamorano. 6120 records from Composición florística del Parque Nacional Huatulco. 1740 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 1270 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 5086 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 1748 records from Flora acuática de Querétaro. 396894 records from NatureServe Network Species Occurrence Data. 51587 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 1858 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 15321 records from Base de datos y catálogo para la utilización, conservación y disponibilidad de Phaseolus en México. 1615 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 678 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 25226 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 253507 records from Flora-On: occurrence data of the flora of mainland Portugal. 235 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 110 records from Niveles y patrones de variación genética del género Abies en México. 404 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 952 records from Investigaciones sobre recursos no maderables de México: biología evolutiva y conservación de plantas del género Chamaedorea. 2620 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 1000 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 4802 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 4240 records from Flora vascular acuática de la cuenca del Río Tamesí. 824 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 580 records from Diversidad y distribución de las comunidades de fitoplancton y peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 1306 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 5020 records from Computarización de la colección de plantas acuáticas mexicanas del Herbario Nacional (MEXU), 2da Etapa. 3512 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 1866 records from Flora de las Barrancas del Cobre. 1572 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 236 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 13350 records from Estudio taxonómico y base de datos del género Muhlenbergia de México. 1606 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 3080 records from Inventario nacional de especies vegetales y animales de uso artesanal. 336 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 80 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 2480 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 9075 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 7634 records from Manual de las gramíneas de Durango. 23558 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 1800 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 2076 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 4680 records from La etnobiología de los recursos nutritivos en las comunidades Tzeltales en los Altos de Chiapas. 99 records from Conocimiento de la macroflora marina de interés económico de las Costas de Yucatán. 356 records from An updated checklist of aquatic plants of Myanmar and Thailand. 3480 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 594 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 25158 records from Ireland's BioBlitz. 1371 records from Banco de información sobre características tecnológicas de maderas mexicanas. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 1408 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 4152 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 1212 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 131189 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 537 records from Patrones de variación espacial y temporal de la biodiversidad fitoplanctónica de los cenotes abiertos de Yucatán. 7040 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 464 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 10501 records from Formación del banco de datos del herbario (UCAM). 106 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 2064 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 6020 records from Computarización de la colección de plantas acuáticas mexicanas del Herbario Nacional (MEXU). 14619 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 5189 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 15578 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 7118 records from Recuento de la diversidad florística de Veracruz. 4798 records from Estudio monográfico de la familia Rhamnaceae en México. 5532 records from Estudio biosistemático del género Bouteloua de México. 4182 records from Estudio florístico de las gramíneas de Zacatecas. 6518 records from Florística de áreas protegidas en el estado de Durango. 17151 records from Base de datos sobre la flora de Durango. 2435 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 6506 records from Inventario florístico de la Sierra de Huautla, Morelos. 4758 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 6 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 15506 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 2070 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 1250 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 86194 records from West African Vegetation Database. 14416 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1626 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 3052 records from Brioflora de la Reserva de Montes Azules, Chis.: Diversidad, Biogeografía y Depauperación por Actividad Humana. 5628 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 6110 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 2064 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás. 208 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 20 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 15002 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 9051 records from Flora Novo Galiciana-Gramineae. 500 records from Plant Specimens of Oiso Municipal Museum. 8 records from UAM Invertebrate Collection (Arctos). 14202 records from Plant specimens of Hokkaido University Museum. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 8784 records from Bryopytes specimens of Akita Prefectural Museum. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 105 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 4688 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 274 records from Herbarium of Lars Levi Laestadius. 68 records from Harold W. Manter Laboratory of Parasitology Collection. 310 records from KNWR Herbarium Collection. 2750 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 3724 records from Ibaraki Nature Museum, Bryophyta collection. 4294 records from Ibaraki Nature Museum, Algae collection. 115011 records from Dataflos. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 264 records from IG TUT paleontology. 342 records from Tartu University, palaeontology collections. 15515 records from Leiner-Herbar Konstanz. 178 records from Raw counts of dinoflagellate cysts in several IODP and DSDP holes. 7 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 1 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 5 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 3 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 3 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 745 records from Collection Paleobotanique de l'Universite Paris 6. 43 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 19 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 6 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 4 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 21 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 42 records from Field Museum of Natural History (Botany) Fungi Collection. 390 records from Inventory of Penessoulou forest (North West Benin). 35 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 104-643A. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 257 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 16 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 1467347 records from NMNH Extant Specimen and Observation Records. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 89 records from CEPEC-Fungi - Coleção Micológica do CEPEC. 28 records from (Table 6) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-906A. 35 records from (Table 5) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-905A. 532 records from Inventory of Bonou and Itchèdè forests in south east of Benin. 15622 records from Universität Salzburg. 1 records from DSMZ Collection of Filamentous Fungi and Yeasts. 4716 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 2185 records from Collection Bernstein - SMF. 4 records from Herbarium Senckenbergianum (FR) - Fungi. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 2 records from Collection Malakologie - SNSD. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 8 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 3761 records from Mountain Invasion Research Network (MIREN) survey. 15 records from Swiss Psyllid (Hemiptera) Collections - Basel. 69 records from Naturhistorisches Museum Mainz, Paleontological Collection. 42 records from MfN - Heteroptera Collection. 15 records from Chrysomelidae of Central Europe. 3 records from MfN - Auchenorrhyncha Collection. 1 records from MfN - Mallophaga Collection. 18 records from GBIF-D Protozoa data collection. 10227 records from Andes to Amazon Biodiversity Program. 8129 records from Seasearch Marine Surveys in Wales. 5185 records from Botanical Garden Collection. 131 records from WA. 31268 records from ANTARCTIC PLANT DATABASE. 10 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 13357 records from Australian Antarctic Division Herbarium. 9 records from Antarctic Marine Protists species checklist. 1508 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 4 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 2 records from Interactive Database of Biodiversity Studies on Terrestrial Arthropod Animals of Korea. 994 records from Korean Ethnobotany Database. 694 records from Factual Database of Native Flora Seeds in Korea. 69 records from Korean Aquatic Vascular Plants. 1 records from Korean Plant Virus Database. 88137 records from Canadian Museum of Nature Herbarium. 183428 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 478 records from CABI Bioscience Fungus Collection. 1 records from CABI Bioscience Nematode Collection. 78126 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 24249 records from Herbario UNAP. 111514 records from The AAU Herbarium Database. 91585 records from Herbarium (ICEL). 22423 records from Herbarium (AMNH). 292665 records from Observational database of Icelandic plants. 6618 records from Real Jardin Botanico, Madrid: MA-Algae. 25127 records from Real Jardin Botanico, Madrid: MA-Musci. 4071 records from Real Jardin Botanico, Madrid: MA-Hepat. 201 records from Real Jardin Botanico, Madrid: MA-Lichen. 215331 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 135628 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 533682 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 20945 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 14971 records from Herbario de la Universidad de Almeria. 30246 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 39833 records from Jardín Botánico de Córdoba: Herbarium COA. 33944 records from Aranzadi Zientzi Elkartea. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 4279 records from Universitat de Girona: HGI-Cormophyta. 37043 records from CIBIO, Alicante:ABH-GBIF. 11209 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 3236 records from Real Jardin Botanico, Madrid: MA-Funhist. 45 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 19130 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 224703 records from Herbario de la Universidad de Sevilla. 11459 records from Herbario de la Universidad de Sevilla, SEV-Historico. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 6560 records from CUBA:Herbario del Jardín Botánico Nacional, La Habana, Cuba: HAJB-Pteridophyta. 59580 records from Institut Botanic de Barcelona, BC. 4065 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 1756 records from EPA'S EMAP Database. 1 records from HMAP-History pf Marine Animal Populations (CoML). 6949 records from NODC WOD01 Plankton Database. 31 records from SeamountsOnline (seamount biota) (CoML). 3210 records from HerbarioHerrerense. 7753 records from Natural Geography In Shore Areas (NaGISA) Dataset. 55 records from Bishop Museum Data (OBIS distribution) (USOBIS). 107 records from GenLink - Genetic diversity of Cerastium holosteoides. 3815 records from Gwaii Haanas Marine Plants (OBIS Canada). 169 records from Bay of Fundy Species List (OBIS Canada). 203794 records from Auckland Museum Botany Collection. 13 records from Database on Forest Disturbances in Europe. 72 records from Scottish Natural Heritage - Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 930 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 40 records from MedOBIS (EurOBIS). 177 records from BioMar (EurOBIS). 30 records from MarBEF Publication Series data (EurOBIS). 7547 records from Botanic Garden of the Finnish Museum of Natural History. 578 records from AIMS - Bioresources Library (OBIS Australia). 8009 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 1053 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 4957 records from MICROBIS database. 63 records from Kystfuruskoger 2015. 43871 records from Herbarium of Jyväskylä University Museum. 918 records from Plant in Baekdu Mountain (KIDR-PL). 2 records from Naturalis Biodiversity Center (NL) - Coleoptera. 26 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 1343 records from martius-munchen-infocomp. 15846 records from Brassicaceae of Canada. 13570 records from Royal Botanical Gardens Herbarium. 984 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 1657 records from Phragmites of Canada. 5095 records from DAO Herbarium Type Specimens. 10 records from Michigan State University Herbarium Lichens. 1216 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 78727 records from Paleobiology Database. 191859 records from herbario. 69 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 19628 records from Bryophytes Collection of National Museum of Nature and Science. 12086 records from Algae Collection of National Museum of Nature and Science. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 109497 records from Plant Specimens of Kurashiki Museum of Natural History. 30150 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 14825 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection, Osaka museum of Natural History. 2884 records from Individual Sightings. 163657 records from Vascular Plant Collection. 524 records from Arctic Ocean Diversity. 475 records from Biodamaz1. 7286 records from IIAPPoa. 2 records from Arizona State University Lichen Collection. 136059 records from Arizona State University Vascular Plant Herbarium. 24794 records from University of Copenhagen Arboretum. 7939 records from Botany registration database by Danish botanists. 47 records from Nivå Bay species list, Zealand, Denmark. 1 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 12843 records from Herbarium Faeroense. 20597 records from Botanical Museum, Copenhagen. Database of type specimens. 168 records from Priest Pot species list, Cumbria, Britain. 3299 records from Botanical Museum, Denmark. Database of registrations of red listed plants. 128454 records from DAV UC Davis Center for Plant Diversity. 41458 records from Herbarium (UNA). 109 records from MEXU/Frutos y Semillas. 31081 records from MEXU/Plantas Vasculares. 8980 records from MEXU/Tipos de plantas vasculares. 40392 records from MEXU/Colección de Briofitas. 5826 records from MEXU/Herbario Los Tuxtlas. 30985 records from MEXU/Asteraceae. 255074 records from Actualización de las bases de datos del Herbario XAL. Fase III. 65 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 141951 records from Plants of Papua New Guinea. 285 records from Invertebrate Paleontology Division, Yale Peabody Museum. 26 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 57 records from Invertebrate Zoology Division, Yale Peabody Museum. 4 records from ATCC Bacteria Collection Catalog. 2 records from CBS Filamentous Fungi Database. 1 records from CECT Spanish Type Culture Collection(Bacteria). 9 records from DSMZ Bacteria. 1 records from DSMZ Fungi. 1 records from Institute of Ecology and Genetics of Microorganisms. 1 records from IFO Bacteria database. 6 records from IFO Filamentous Fungi. 8 records from Japan Collection of Microorganisms(Bacteria). 1 records from Japan Collection of Microorganisms(Fungi). 2 records from AlgaTerraMovies. 452 records from Algaterra Types. 1004 records from Bridel Herbar. 754 records from Sistemática y distribución actual de los Agave spp mezcaleros. 10606 records from Desmidiaceae Engels. 603 records from Desmidiaceae Mollenhauer. 2160 records from Flora exsiccata Bavarica. 9 records from (Supplement 3) Dinoflagellate cyst count data by species of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 355 records from GEO Biodiversity Day. 200094 records from Herbarium Berolinense. 112547 records from Herbarium Willing. 10 records from Lichen Herbarium Berlin. 1534 records from PonTaurus collection. 27225 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 6 records from Desmidiaceae Rostock. 22844 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 4695274 records from Observations du Conservatoire botanique national du Bassin parisien.. 97770 records from Biologiezentrum Linz. 46189 records from Herbarium Senckenbergianum Görlitz (GLM). 313082 records from United States National Plant Germplasm System Collection. 679060 records from The System-wide Information Network for Genetic Resources (SINGER). 252389 records from Israel Nature and Parks Authority. 54 records from Banc de dades de biodiversitat de Catalunya-MolusCat. 3596 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 121 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 5614 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1470 records from The Erysiphales Collection at the University Halle-Wittenberg. 24 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 422 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 51 records from Sea Algae. 186 records from Green Algae. 1396 records from IndOBIS, Indian Ocean Node of OBIS. 531 records from Biological Collection, National Institute of Oceanography, Goa, India. 2 records from TSB Lichen Herbarium. 704 records from DSMZ Collection on Plant Cell Cultures. 37515 records from Nordic Genetic Resources. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 96017 records from USU-UTC Specimen Database. 6817 records from AWI-Herbarium Marine Macroalgae. 238 records from UF Invertebrate Zoology. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 9754 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 15666 records from Institut Botanic de Barcelona, BC-Histórico. 21380 records from Bryophyte collection. 34488 records from Herbarium de Geo. B. Hinton, México. 1935 records from HBGBryophyta - Herbarium Hamburgense. 19890 records from HBGSpermatophyta - Herbarium Hamburgense. 17517 records from Impetus - Herbarium Hamburgense. 42 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 268 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Juergen Homeier. 420 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 2519 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 41 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 27 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 127 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 17 records from Visual Plants (144.41.33.158) - Private collection of Vindas Jorge, Costa Rica. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 3 records from Visual Plants (144.41.33.158) - Private collection of Barbara Kueppers. 21 records from Visual Plants (144.41.33.158) - Private collection of Helmut Dalitz. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 50 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 9 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Daniel Piechowski. 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 133 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 545 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 78 records from Electron Micrograph Database - Marine Specimens. 182 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 2586 records from Plant Specimens of Lake Biwa Museum. 15879 records from Angiosperm specimens of Iwate Prefectural Museum. 36992 records from Vascular Plants Collection of Sagamihara City Museum. 7127 records from MEXU/Asclepiadaceae. 437895 records from Harvard University Herbaria. 30915 records from Vascular plants of south-central China. 82611 records from Specimen Database of Colorado Vascular Plants. 231 records from Plotmatrix 2008 Alb Hainich Schorfheide Durchgang1. 195 records from Visual Plants (144.41.33.158) - Private collection of Eberhard Fischer. 235 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 1242 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 504 records from Visual Plants (144.41.33.158) - Herbarium specimen from "USJ", Costa Rica. 137 records from Visual Plants (144.41.33.158) - Herbarium specimen from "BIEL", Germany. 125112 records from BioGIS - Vascular plants - A. Danin's grid database. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 4 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Annette Wolter. 4 records from DSMZ Prokarya Collection Catalogue. 21 records from DSMZ Collection of Plant Viruses. 17349 records from Herbarium BSG Vascular Plants. 71328 records from inatura - Erlebnis Naturschau Dornbirn. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 11622 records from French Grapevine Genetic Resources Center. 489 records from Galapagos grasses and sedges. 4124 records from Herbario de la Universidad de La Laguna:TFC-Bry. 1 records from ORN. 67 records from Herpetology. 959667 records from EURISCO, The European Genetic Resources Search Catalogue. 309 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 78 records from Electron Micrograph Database (Australian Antarctic Data Centre). 5060 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 20 records from NCOS1959_Crustacea (OBIS China). 33 records from NCOS1959_Mollusca (OBIS China). 29 records from Database of invertebrates collected in Mongolia. 88498 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 243 records from Thistles species and abundance. 15617 records from CVRD - Herbário da Reserva Natural Vale. 5 records from Aves MZS. 1000 records from Plant Specimens of Taga Town Museum, Shiga Pref., Japan. 126119 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 30625 records from Kochi Prefectural Makino Botanical Garden. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 10635 records from Bryophyta Specimens of The Nagoya University Museum. 1110 records from MEXU/Colección Histórica. 7101 records from MAR - Herbário do Maranhão. 28 records from MAL. 21 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 1267 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 106732 records from USGS South Florida Fish and Invertebrate Assessment Network Braun Blanquet. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 2903 records from UAM Herbarium (ALA), Algae Collection (Arctos). 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 9609 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Chingaza. 35 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 259575 records from Staffordshire Ecological Record - SER Site-based Surveys. 95173 records from Biodiversitätsdatenbank des Landes Salzburg. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 710 records from English Nature Berkshire SSSI Records. 7684 records from Seed bank grassland. 2396 records from Herbarium BSG Bryophyta. 54458 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 39 records from Naturalis Biodiversity Center (NL) - Aves. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 33 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 2 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 2251 records from Plant Systematics Laboratory, Ajou University, Korea. 57 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 425 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 1971 records from Flora acuática vascular del estado de Hidalgo: Cuenca hidrológica del Río Moctezuma, México. 24439 records from Herbario de la Universidad de Arizona, EUA. 84569 records from Repatriación de datos del Herbario de Arizona (ARIZ). 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 82953 records from Vascular Plants, Observations, Oslo (O). 9211 records from Árboles y Arbustos Nativos para la Restauración Ecológica y Reforestación de México (IE-DF,UNAM). 1443 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 5566 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 59544 records from Programa de repatriación de datos de ejemplares mexicanos. 486 records from Flora ficológica marina de Tamaulipas. 49892 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 68 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1614 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 3329 records from Universitat de València, Colecciones de Criptógamas: VAL_Briof. 1 records from Christopher Walker collection of Glomeromycotan fungi. 32 records from UCM Amphibian and Reptile Collection (Arctos). 232190 records from Oklahoma Vascular Plants Database Provider. 74018 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 62 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 316 records from Moss species from Heard Island, 1987 and 2000. 3 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 485 records from BÜG. 357 records from LaBoOb02. 18 records from Pfrimmersbachtal. 89 records from Klutensee. 70 records from Überall ist Wunderland. 157 records from DJH. 124 records from Am Moosangerweg. 69 records from Frau Voss. 370 records from Danielsberg (Mölltal, Kärnten). 25 records from Streuobstwiese RSG (Cham). 309 records from Naturschutzgebiet Sistig-Krekeler-Heide. 134 records from AKG-Gelände (Bensheim). 198 records from FFH-Gebiet Ahrbachtal. 75 records from Botanischer Garten (Saarbrücken). 89 records from Trockenhang Greinhartsberg Edelfingen. 743 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 90 records from Hamberger Brücke / Würmtal (Pforzheim). 75 records from Artenvielfalt auf den Elbwiesen (Dessau). 18 records from Schulgelände (Wetter). 431 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 50 records from Sandhofen. 167 records from Kernberge und Umgebung (Jena). 192 records from Schlichemquelle (Tieringen/Meßstetten). 188 records from Mooswald (Freiburg). 551 records from Gemeinde Sursee. 174 records from Gewann Krampf (Heilbronn). 12 records from Angelberger Forst - Klassen 3 a und 3 b. 320 records from Naturschutzstation Schmidsfelden. 173 records from Landschaftspflegehof (Berlin). 457 records from Naturschutzgebiet Bausenberg. 183 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 12 records from Altholzparzelle Eilenriede Hannover. 53 records from Schulhof Bühlschule Giengen. 529 records from Schlern - (Bozen). 821 records from GEO Hauptveranstaltung Tirol (Innsbruck). 61 records from Schulgelände IGS Kaufungen. 165 records from Schule Sulzbach (Oberegg). 271 records from Zukünftiges NSG Höftland/Bockholmwik. 95 records from Artenbestimmung. 547 records from Königstetten. 109 records from Frauenholz (Holzmaden). 329 records from Freiburger Tag der Artenvielfalt. 64 records from Erzental (Oberotterbach). 174 records from Langes Tannen (Uetersen). 231 records from Gelände des IVL (Zeckern). 143 records from Stausee (Oberdigisheim/Meßstetten). 113 records from Naturschutzgebiet Bausenberg (Niederzissen). 440 records from Erlengraben/Lipp-Tal (Östringen). 147 records from Wald und Wiese am Buchwald. 210 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 263 records from NSG Karwendel. 180 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 411 records from Neckartalsüdhang (Horb). 174 records from Umgebung der Gesamtschule Hamburg-Winterhude. 89 records from Langes Tannen. 58 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 93 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 101 records from Schulgarten Huttenheim (Philippsburg/Baden). 152 records from Sonnentaugemeinschaft. 76 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 28 records from Artenvielfalt der Nordsee - Helgoland. 158 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 189 records from Philosophenwald und Wieseckaue in Gießen. 34 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 59 records from Artenvielfalt auf Restbauernhof. 65 records from Wiese und Weide am Waldrand von Gusterath. 73 records from Blumenrather Heide / Virneburg. 264 records from Cuxhavener Küstenheiden. 43 records from Umgebung von Schorndorf. 721 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 77 records from Danisco-Wiese. 297 records from nazza. 22 records from Birkenpilz. 168 records from katzenbuckel. 180 records from Promberg1. 303 records from Biologische Station im Kreis Wesel. 346 records from GEO-Hauptveranstaltung (Insel Vilm). 584 records from GEO-Hauptveranstaltung (Duisburg). 86 records from Wanderweg am Windebyer Noor (bei Eckernförde). 479 records from BUND - Dassower See (Lübeck/Dassow). 280 records from Wildes Bremer Leben im Park. 100 records from Entdeckertour am Muldestausee. 164 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 77 records from Unser Schulgelände. 397 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 113 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 20 records from Nottekanal, Klasse 7 - 10. 77 records from Luch Niederlehme, Schüler der Klasse 7. 21 records from Stadtbiotop Ulrichteich. 282 records from Pilstingermoos. 229 records from Artenfülle um das Schalkenmehrener Maar. 112 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 186 records from Riedensee. 72 records from Streuobstwiese Kattenhund (Schleswig). 265 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 317 records from Gurgltal (Tarrenz). 16 records from Absolute abundances of organic-walled dinoflagellate cysts from 116 marine surface samples. 39 records from Überschwemmungsgebiet der Wied. 373 records from 20 Jahre Naturschutzgebiet Dreienberg. 32 records from Hüttenseepark (Meißendorf). 28 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 80 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 153 records from Heinersdorfer Sumpfwiese. 1 records from Schaalbach. 99 records from 4. GEO-Tag in Eberbach. 35 records from Deutsche Schule Budapest. 210 records from schulgarten. 33 records from GEO-Hauptveranstaltung Bodden (Vilm). 86 records from NSG Nollig. 161 records from Pottundkopp. 178 records from Knechtweide (Kohlfurth). 2 records from uno city. 5 records from Landesgartenschau. 153 records from Wildkräuter. 40 records from Schulumgebung Grüterschule, Rheine. 173 records from Wald am Schloss Wittgenstein Bad Laasphe. 82 records from Industriegebiet (Kempen). 68 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 134 records from Ökostation (Freiburg). 88 records from Bergbaufolgelandschaft am Muldestausee. 116 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 73 records from Regionalpark(Hattersheim). 32 records from Langes Tannen in Uetersen. 84 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 76 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 50 records from Schulhof Goethe-Gymnasium (Emmendingen). 230 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 146 records from Kiesbagger (Mittelhausen). 55 records from Biotop Binsenwiesen (Wehrheim/Taunus). 102 records from NSG Berschau - Auengebiet (Neustadt / Wied). 54 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 39 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 313 records from Gemeindegebiet Weikendorf (Marchfeld). 152 records from Umgebung der Gesamtschule Winterhude (Hamburg). 161 records from Lebensraum Gesamtschule (Langerwehe). 44 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 68 records from Tiergarten (Zeitz). 65 records from Natur aus zweiter Hand am Muldestausee. 69 records from Schulgelände Schule auf der Aue, Münster. 85 records from "Tre Pini" (Montebelluna, Italien). 50 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 201 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 164 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 56 records from Schloß Türnich (Kerpen). 131 records from Unser Schulhof - eine Apotheke. 106888 records from Field Museum of Natural History (Botany) Bryophyte Collection. 149 records from Quarrendorfer Landschaftsschutzgebiet. 149 records from Faberpark (Nürnberg/Stein). 23 records from Unser Schulhof. 75 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 210 records from Streuobstwiese Kugelberg (Ulm). 108 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 135 records from Wiese am Waldrand (Gurtweil). 47 records from Südwestlich der Parkwiesen. 63 records from Wismar Bucht coast-watching. 104 records from Urwald 1 (Bad Waldsee). 56 records from Schulprojekt (Bremen). 192 records from Fuldaaue (Stadtgebiet Fulda). 257 records from Stadtgebiet (Dannenberg). 77 records from Muehlenbach bei Friesheim. 225 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 133 records from Renaturierung Werse (Innenbereich Beckum). 67 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 501 records from Bergkamen- Bergehalde Großes Holz. 7 records from Boraginaceae (Cynoglossum cherangauiense). 33 records from Lüner Holz (Lüneburg). 129 records from Stadt Königs Wusterhausen. 129 records from Stadtpark Sulzbach-Rosenberg. 139 records from Lindau im Bodensee. 105 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 42 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 126 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 75 records from Schulhof und Anlagensee in Nellingen. 136 records from Tiergarten Straubing. 62 records from Vorderer Tiergarten (Dessau). 101 records from Bizzenbachtal (Wehrheim/Taunus). 136 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 140 records from Werremündung im Schwarzatal. 25 records from Klimaoasen in Köln. 159 records from Schlattstaller Tal (Lenningen). 95 records from Naturschutzgebiet Müchelholz (Mücheln). 153 records from arthropods on Plantago lanceolata. 1834 records from Eppingen und Umgebung. 96 records from Steinbruch Haas Stuttgart-Münster. 50 records from Küste Wismar-Wendorf bis Hoben. 29 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 18 records from Hemmerder Schelk (Unna). 443 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 59 records from Weidenhüttendorf an der Würm (München). 206 records from renaturierter Main (Kemmern bei Bamberg). 52 records from Unterbrucker Weiher. 164 records from 3. Tag der Artenvielfalt Hockenheim. 102 records from Prophetensee Quickborn. 97 records from Halberg bei Neumorschen. 60 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 64 records from Hintere Halde. 52 records from Steinbruch Pluwig. 88 records from Lebensraum Stadt und Park. 114 records from Schussenaue (Weingarten). 189 records from Wupperaue bei Kemna (Wuppertal). 639 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 113 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 12 records from An der Ohm, (Wettsaasen). 28 records from Freiheitsring (Frechen). 25 records from Schulgarten Paul-Schneider-Schule, Münster. 28 records from Artenvielfalt der Nordsee - Sylt. 9 records from Spandau HBO. 72 records from Dreilinden Gymnasium-Schulgelände. 36 records from Maschwiesen Laatzen. 98 records from Himmelmoor. 137 records from Altenburg bei Bamberg. 260 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 68 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 144 records from Naturerlebnisraum Koppelsberg. 158 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 322 records from Walldorf-Wiesloch: "Natur über den Gleisen". 202 records from Innenstadt Göttingen - Natur Zuhause. 144 records from Mißmahlsche Anlage. 42 records from Teich Berlin Wuhlheide. 47 records from Ruhrwiesen bei Neheim-Hüsten. 58 records from Schulgelände Städtisches Gymnasium. 17 records from Artenvielfalt im Umfeld der Burgwegschule. 179 records from Naturgarten Langenholtensen. 105 records from VSN-Wiese. 96 records from Arteninventar rund um den Rannahof. 249 records from Tag der Artenvielfalt. 71 records from Artenvielfalt auf dem Schulgelände. 299 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 39 records from Schulgelände SGD/Viersen. 317 records from Unna-Mühlhausen, Wiesen. 717 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 43 records from Naturalis Biodiversity Center (NL) - Hemiptera. 1015 records from Caracterización vegetal y rasgos funcionales de plantas colectadas en un gradiente altitudinal de bosque altoandino a páramo en el Santuario de Fauna y Flora Iguaque. 1 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB04 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 423 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 2 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 1 records from Microplankton abundance in the euphotic zone of the Aegean and Levantine Seas in Sepmember-October 1987. 78 records from (Table 1) Count data of organic-walled dinoflagellate cysts in surface sediment samples from the Benguela System. 2 records from Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region. 137072 records from USF Herbarium. 63 records from GenLink - Genetic diversity of Veronica chamaedrys. 267699 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 42 records from Results of palynological analysis of Hole 302-M0004A. 162 records from Colecta de maíces nativos en regiones estratégicas de la Península de Yucatán. 357 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 3704 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 1 records from Foraminifera abundance of Hole 39-357. 4984 records from Herbier Ecole de Faune. 932030 records from Atlas Flora Danica. 4 records from Foraminifera abundance of Hole 17-171. 2056 records from Spring bryophyte flora of Salpausselkä (Ulvinen 1955 & Juutinen 2006). 13 records from UMMZ Herpetology Collection. 150 records from Vegetatively propagated Allium collection. 37 records from (Appendix A) Dinoflagellate counts in surface sediments of cores taken in the North Pacific. 557 records from Census of the threatened species of Benin. Data mobilized in the framework of BID-AF2015-0066-REG project funded by EU. 61 records from Lichens of North-Eastern Poland. 2034 records from Herbarium of Namur. 302 records from National Botanic Garden Belgium - Martius. 2 records from Foraminifera abundance of Hole 61-462. 89170 records from Natural History Museum, University of Tartu. 2 records from Microfossil abundance of Hole 35-323. 6 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 5637 records from Computarización del Herbario ENCB. Fase II. Base de datos de los ejemplares de la familia Burseraceae y Nyctaginaceae y base de datos digitalizada de los ejemplares tipo de plantas vasculares del Herbario de la Escuela Nacional de Ciencias Biológicas. 5 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 105551 records from University of British Columbia Herbarium (UBC) - Algae Collection. 9 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 63261 records from Herbarium of Umeå University (UME). 58 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 209172 records from Mosses (S). 3 records from Amphibian observations from Nida Valley. 243 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 169 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 182771 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 537570 records from Field Museum of Natural History (Botany) Seed Plant Collection. 90 records from Herbario MAIA, colección de Ericas del INIA-CIFOR. 101563 records from MBML-Herbario - Herbário Mello Leitão. 3279 records from Espèces vasculaires endémiques et orchidées (CITES). 107619 records from MPM Milwaukee Public Museum Herbarium. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 2159 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 1201 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 2 records from Benthic foraminifera abundance of Hole 84-567A. 1 records from Benthic foraminifera abundance of Hole 84-569. 1 records from Benthic foraminifera abundance of Hole 84-569A. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Benthic foraminifera abundance of Hole 84-569, Part 1. 12 records from Range table from benthic foraminifers in ODP Hole 143-865A. 21 records from Range table from benthic foraminifers in ODP Hole 143-866A. 2 records from Range table from benthic foraminifers in ODP Hole 144-879A. 4204 records from Seasearch Marine Surveys in Ireland. 1005 records from English Nature Grassland Survey 1995. 3 records from Range table from benthic foraminifers in ODP Hole 149-900A. 20 records from Range table from benthic foraminifers in ODP Hole 159-959D. 14 records from Weevils of Wales and England. 26440 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 304 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 276 records from PSU-Seagrass Collection. 10 records from Range table from benthic foraminifers in ODP Hole 171-1049A. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 1 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 2 records from Range table from benthic foraminifers in ODP Hole 171-1052E. 7 records from Distribution of Upper Cretaceous deep water agglutinated foraminifera in sediments of the North Atlantic and its marginal seas (Tab. 1). 59906 records from Polish gene bank – passport data of plants accessions which are important in human life. 1 records from Dinoflagellate abundance of Hole 81-552. 2 records from Dinoflagellate abundance of Hole 81-553A. 7 records from Dinoflagellate abundance of Hole 81-555. 1 records from Dinoflagellate abundance of Hole 81-552. 3 records from Dinoflagellate abundance of Hole 81-552A. 2 records from Dinoflagellate abundance of Hole 81-553A. 3 records from Dinoflagellate abundance of Hole 81-554. 1 records from Dinoflagellate abundance of Hole 81-554A. 20 records from Dinoflagellate abundance of Hole 81-555. 5 records from Dinoflagellate abundance of Hole 14-144. 1 records from Dinoflagellate abundance of Hole 22-214. 5 records from Dinoflagellate abundance of Hole 28-270. 1 records from Dinoflagellate abundance of Hole 28-274. 27 records from Dinoflagellate abundance of Hole 94-607. 4 records from Dinoflagellate abundance of Hole 94-607A. 11 records from Dinoflagellate abundance of Hole 94-611. 28 records from Dinoflagellate abundance of Hole 94-611C. 1 records from Pollen and spore abundance of Hole 42-379A. 8 records from Pollen and spore abundance of Hole 42-380. 7 records from Pollen and spore abundance of Hole 42-380A. 1 records from Pollen and spore abundance of Hole 42-381. 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-900A. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-907A. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-911A. 12 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1168A. 4 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1169A. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170A. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 23 records from Results of palynological analysis of Hole 302-M0002A. 4 records from Results of palynological analysis of Hole 302-M0004B. 1045716 records from Belgian IFBL Flora Checklists (1939-1971). 46 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 68 records from Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2). 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 2 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 649 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 172 records from EEIKO Base de datos sobre plantas invasoras. 15 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 51 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 1181 records from Spécimens d'herbiers de G. Fenoul (FEN). 2 records from Middle Miocene microflora of Zidlochovice (Czech Republic). 990 records from Perchtoldsdorfer Heide. 144 records from Naturpark Drömling. 242 records from Schwanheimer Wald. 262 records from Freiburger Netzwerk Artenvielfalt. 157 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 50 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 156 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 150 records from Berkel. 35 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 51 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 30 records from NSG Dellwiger Wald, Dortmund. 357 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 124 records from NSG Haunestausee, Hauneteiche. 49 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 29 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 28 records from Biosphärenreservat Münsinger Alb. 32 records from Töpinger Mischwald. 25 records from Phragma-Thermis/Thessaloniki. 38 records from Flora und Fauna in unserer Kita. 13 records from Klosterwald Itzehoe. 12 records from Waldstück am Schullandheim Bad Bederkesa. 9 records from Auenwiesen und Trockenrasen. 57350 records from Colorado State University Herbarium. 24204 records from EKY_Darwincore. 56137 records from MISS_DC_01MAR2006. 526 records from FernsDarwinCore. 8974 records from NCSU_Darwincore. 391 records from Lustadter Wald .. 66 records from Waldwandel in Monschau-Mützenich-Boverei. 57 records from Gymnicher Mühle. 166 records from Kohlstattbrunnental. 90 records from Naturnahes Tal in Siena. 259908 records from R. L. McGregor Herbarium Vascular Plants Collection. 47 records from Departamento de Investigación y Experiencias Forestales de Valonsadero de la Junta de Castilla y León: JCYL-Fungi. 10921 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1796 records from EDIT - ATBI in Gemer area (Slovakia). 69 records from ELM paleontology. 1092244 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 6534 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 1 records from Vertebrate specimens of Jyväskylä University Museum. 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 38917 records from Gunma Museum of Natural History, Vascular Plant Specimen. 35489 records from MEXU/Colección de Plantas Acuáticas. 525 records from Artenvielfalt am Schlern. 492 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 173 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 152 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 607514 records from Plant. 14411 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 145153 records from DUKE Bryophyte Collection. 78931 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 3773 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 627267 records from Biological and palaeontological collection and observation data MNHNL. 20970 records from Sukkulentensammlung Zürich. 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 108676 records from Botany Division, Yale Peabody Museum. 1 records from Entomology Division, Yale Peabody Museum. 3 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 80928 records from Paleobotany Division, Yale Peabody Museum. 4 records from Vertebrate Paleontology Division, Yale Peabody Museum. 382 records from Tag der Artenvielfalt im Taubental. 64 records from VFD-RP, Taunus: Bergweide Dehe. 178 records from KU Museum of Invertebrate Paleontology. 288 records from Collection Pisces SMF. 6270 records from HUTO - Herbário da Universidade de Tocantins. 6 records from Collection Mollusca SMF. 34 records from Collection Echinodermata fossil SMF. 62 records from Collection Mikropaläobotanik SMB. 96364 records from Herbarium Senckenbergianum (FR). 185 records from Collection Aves (bird skeletons) SMF. 1660 records from Collection Paläobotanik SMB. 7 records from Collection Bryozoa SMF. 138 records from Collection Cnidaria fossil SMF. 7 records from Collection Thysanoptera SMF. 2437 records from Collection Messelpaläobotanik SMB. 2 records from Collection Tunicata SMF. 1 records from Collection Tardigrada SMF. 269618 records from SINGER Coordinator. 3538 records from NHT_flora. 297 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 36 records from Type Localities for organisms and fossils first described from Antarctica. 213 records from The genetic and morphological diversity of Nance (Byrsonima crassifolia) en Yucatán, Mexico. 11955 records from MEXU/Leguminosae. 2618 records from MEXU/Agavaceae. 3439 records from MEXU/Flora de Oaxaca. 989 records from MEXU/Pinaceae. 894 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Algae. 34958 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 11098 records from Herbario de Universidad de Murcia: MUB. 53 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 1 records from Joseph F. Rock Herbarium. 1261 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 84850 records from Database of Native Plants in Taiwan. 124909 records from National Inventory of Swiss bryophytes. 2357 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 51454 records from Bryophyte Collection - University of Washington Herbarium (WTU). 503 records from Mycological Collection - University of Washington Herbarium (WTU). 269 records from Lichen Collection - University of Washington Herbarium (WTU). 5 records from Benthic macrofauna abundance and biomass in surface sediment during cruise CD86. 2 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 12 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 5 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 85090 records from University of Ghana - Ghana Herbarium. 1988 records from Plant of Folklore (KIDR-PL). 599 records from NHT flora. 273 records from E39 Lyngdal - Ålgård. 2771 records from Ecología, manejo y conservación de Quercus potosina y Q. eduardii en la Sierra Fría, Aguascalientes. 536 records from River macroinvertebrate data for 2005 and 2006. 161563 records from Herbarium of Taiwan Forestry Research Institute. 1423 records from Inventaire National du Patrimoine Naturel : CBN du Massif Central. 191 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 10215 records from Seasearch Marine Surveys in Scotland. 1 records from Insect Arthropods (KIDR-IN). 199 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 23610 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 163418 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 2512 records from UAM Earth Sciences Collection (Arctos). 128 records from Plant Living in Water (KIDR-PL). 2588 records from Situación actual del búho manchado mexicano (Strix occidentalis lucida) y de los Strigiformes de la Reserva de la Biósfera La Michilía. 77 records from Shannon Index and species richness for plants. 1 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 16 records from Caracterización ecológica y monitoreo del Parque Nacional Sistema Arrecifal Veracruzano: Primera Etapa. 5625 records from Plant inventory of W Biosphere reserve (North-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 88175 records from Herbario Amazónico Colombiano. 678 records from Plants from India in the vascular plant herbarium, Natural History Museum at the University of Oslo (NHM-UiO). 2 records from Plant - Plant Virus (KIDR-PL). 7513 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1388 records from Plant - Seed (KIDR-PL). 3931 records from Vegetation data from phytosociological studies of the forests on the Fosen peninsula. 2054 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1495 records from Macroalgas marinas de la costa noroccidental de Baja California, México. 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 1159 records from TransForest vegetation data. 741 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 46346 records from Banco de datos florísticos del Herbario CHAP. 489631 records from Precis Plant Data. 2970 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 2 records from Carpatica Operation. 53 records from Estado actual de las especies de macroalgas introducidas e invasoras en la costa Pacífico de México. 1 records from Museum of Southwestern Biology, Division of Arthropods. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 4591 records from WII Herbarium Dataset. 168 records from IPAS Kitanglad. 2661 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 195727 records from National vegetation diversity inventory and mapping plan. 86834 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 9506 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2455 records from Algae (NSMK-AG). 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 513 records from La vegetación y flora de las Lagunas de Catazajá-Emiliano Zapata. 9 records from BLS Lichen Database: Wales. 74 records from Estudio poblacional de Turbinicarpus valdezianus en el Cañón de las Bayas, Municipio de Arteaga, Coahuila. 31061 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 1340 records from Floral visits on plants, InsectScale 2008. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 7 records from A new species, genus and tribe of Sapotaceae, endemic to Madagascar. 5664 records from Vascular Herbarium, NMBU. 4508 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 763 records from Briòfits d'Andorra. 505450 records from Wetland Inventory (NV). 9 records from Photodocumentation_of_Antarctic_Peninsula_Lichens. 27062 records from Integración de bases de datos, actualización y sistematización de la colección de flora del Herbario Eizi Matuda (HEM). 955 records from Diversidad y distribución altitudinal de maíces nativos en la región de los Loxicha, Sierra Madre del Sur Oaxaca. 2348 records from Evaluación de conservación de especies de Cactaceae en la Reserva de la Biosfera Tehuacán-Cuicatlán. 32 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 28772 records from The DNA and Sample Repository at AIT. 176 records from Jardín Botánico Uniamazonia JBUA. 2649 records from KTU Pteridophyta. 1703416 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 1 records from Naturalis Biodiversity Center (NL) - Porifera. 1004 records from National Trust - Sutton Hoo species data held by The National Trust.. 79481 records from UPCB - Herbário do Departamento de Botânica. 1781 records from Soft Wheat French National Collection. 209 records from pflanzendiversitaet_2008_sch_zweiter_durchgang. 11036 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 440 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 1458 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 3488 records from Faun. 34158 records from Bosque Mesófilo de Montaña de México. 8078 records from tef-database. 68 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 1551 records from fundo. 447 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 27 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 44 records from Parcela Permanente en el Pantano Martos. 3060 records from condoncollection. 194 records from Queensland Museum provider for OZCAM. 7 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in Quaternary sediments from ODP Hole 189-1172A. 4293 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 148 records from Monitoreo biológico en la cuenca Sonso, campaña Agua ARA - RARE - CVC – Asociación Calidris. 2436 records from Seasearch Marine Surveys in the Channel Islands. 887 records from ARKO gamle edellauvtrær. 687 records from Heritage Trees of Ireland. 60197 records from Flora d'Andorra. 1 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 3540 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 14074 records from HURB - Herbário do Recôncavo da Bahia. 95 records from CUMV Amphibian Collection (Arctos). 9834 records from National System of Protected Areas in Poland - Plants. 924 records from Restauración, protección y manejo de ecosistemas del Parque Nacional Pico de Orizaba y su área de influencia, en colaboración con SEMARNAT, CONANP, CONAFOR y PROFEPA. 40 records from Taxonomic study of the genus Atkinsonia Stainton, 1859 (Lepidoptera, Stathmopodidae) in China, with descriptions of two new species. 543000 records from Aarhus University Palm Transect Database. 5953 records from Elaboration du tarif de cubage multispécifique. 1464 records from University of Amsterdam (NL) - Páramo vegetation research, Santa Marta and Perijá, Colombia. 15827 records from ArtenFinder. 2 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1171D sediments. 607 records from Inventory of Bassila forest (North-Benin). 720222 records from Lund Botanical Museum (LD). 23396 records from Specimens of livervort herbarium KPABG. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 50019 records from vegetation releves on grassland gridplots 2007-2009. 7376 records from The Vascular Plant Collection at the Herbarium Tubingense. 154 records from GenLink - Genetic diversity of Trifolium repens. 291 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 12649 records from Herbario CTES Plantas Vasculares. 1275 records from Actualización de la base de datos de Cactáceas del Valle de Tehuacán – Cuicatlán (Puebla, Oaxaca). 585 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 12579 records from Plantas vasculares de la Sierra Tarahumara -listado florístico, etnobotánico e histórico-. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 5074 records from Census of medicinal plants of Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 3426 records from National Trust - Ickworth species data held by The National Trust.. 752482 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 4926 records from HVAT - Herbário do Vale do Taquari. 66 records from Genebank, National Institute of Agrobiological Sciences. 112 records from iHerbarium. 112 records from Monitoreo biológico en la cuenca Dagua - Subcuenca Bitaco, campaña ARA - RARE - CVC – Asociación Calidris. 2452 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 1280581 records from Geographically tagged INSDC sequences. 24125 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 12 records from Collembola Collection. 17166 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 425 records from 2000-2003 RBWM WHS Surveys. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 77102 records from vegetation releves on grassland gridplots in 2007. 2 records from Field Museum of Natural History (Botany) Lichen Collection. 6542 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 2917 records from Quadrige. 1972 records from Threatened species recorded in protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID Regional project BID-AF2015-0066-REG and funded by EU. 14574 records from TEPB - Herbário Graziela Barroso. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 36656 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 208 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 6349 records from HTSA - Herbário do Trópico Semiárido. 537 records from flower visitor interactions 2007 Schwäbische Alb. 1 records from Fitoplancton de los bloques de exploración de hidrocarburos COL 4 Y 5 del Caribe colombiano. 2344 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 7973 records from Herbarium togoense. 10179 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 49 records from Aphidoidea Collection. 1213886 records from Norwegian Species Observation Service. 23199 records from HVASF - Herbário Vale do São Francisco. 1102 records from Plantas laguna El Tinije. 21460 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 8 records from Casual records for Scottish Wildlife Trust reserves - Unassessed data. 24 records from William Nylander lichen collection. 90083 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Herbier Husnot, Hepatica Galliae. 2116 records from SANBI: Rare and Threatened Plants (Cape Floristic Region, 1864-2008). 21439 records from HST - Herbário Sérgio Tavares. 2666 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 701 records from Merseyside BioBank Active Naturalists (verified). 8158 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 24971 records from Colección de Herbario. 265 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 541 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 7416 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 3 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 64 records from Chenopodium vulvaria. 116762 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 6442 records from R-Tipos - Herbário do Museu Nacional - Tipos. 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 5370349 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 961 records from Herbier_CNSF. 50 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 88 records from CFU of pink-pigmented facultative methylotrophs per gramm leaf fresh weight. 2784 records from Kauai Invasive Species Committee - Pest Surveys - 2001-2011. 95 records from forest_soil_fauna_densities_grouplevel_2008. 53 records from Programa regional para la caracterización y el monitoreo de ecosistemas de manglar del Golfo de México y Caribe Mexicano: Península de Yucatán. 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 1867 records from Rocky Shore Macroalgae. 959 records from Los musgos de México. 4607 records from Árboles mexicanos potencialmente valiosos para la restauración ecológica y la reforestación. 2489 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 53 records from GenLink - Genetic diversity of Bromus hordeaceus. 1 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2290 records from Inventario florístico en la zona de Bahía Magdalena e islas adyacentes, Baja California Sur. 926 records from John Muir Trust - Knoydart Bryophytes, 1990. 8389 records from SBT-Living. 1248 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 983 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 411283 records from Bernice P. Bishop Museum. 1333 records from Análisis de la distribución y estructura de las poblaciones de Echinocactus platyacanthus Link et Otto, en el Valle de Zapotitlán, Puebla. 2385 records from Biodiversidad, hábitat y manejo en el Parque Nacional Pico de Tancítaro, Michoacán, México. 67 records from CUMV Reptile Collection (Arctos). 50749 records from FURB - Herbário Dr. Roberto Miguel Klein. 1837 records from Fremmede arter - spredningsvegen «import av planteprodukter». 1668 records from Helechos de la jurisdicción de Corantioquia. 6735 records from National Invasive Species Database. 10 records from Lichens of Knyszyn Forest. 5170 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 152 records from Shannon Index and species richness for herbivores. 54 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 355 records from Cuarenta y ocho especies de la flora de Chiapas incluidas en el PROY-NOM-059-ECOL-2000. 19297 records from Irish Crop Wild Relative Database. 265315 records from Carnet en Ligne. 9080 records from CRI - Herbário Pe. Dr. Raulino Reitz. 714 records from Flora vascular y endemismos de las partes altas de varios macizos montañosos de Querétaro y norte de Michoacán-1ra Fase. 115 records from SuLaMa plant monitoring. 5202 records from HUEG - Herbário da Universidade Estadual de Goiás. 40 records from DGGE profiles of selected Alphaproteobacteria from leaf samples. 89 records from Estudio de la microflora de los suelos de la zona de preservación ecológica 'La Uva' (Sinaloa) con vegetación de selva baja caducifolia empleando taxonomía molecular. 21861 records from Staffordshire Ecological Record - SER Species-based Surveys. 192 records from Herbario IES San Isidoro de Sevilla. 17228 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 118271 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 24 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 154 records from Sorensen distance for herbivores. 111 records from Mollusca Collection. 10464 records from Seed collection – Dead seeds for evaluation and observation purposes. 4150 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 1 records from UTEP Vertebrates. 28 records from ECatSym: Electronic World Catalog of Symphyta. 7642 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 6768 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Mendéz, Tolima. 17324 records from Condon Fossil Collection. 34 records from Levantamento de Herbáceas da RDS Uatumã. 27059 records from Colección del Herbario PSO de la Universidad de Nariño. 19598 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 18 records from CU Invertebrate Paleontology. 18053 records from UFACPZ - Herbário da Universidade Federal do Acre. 763698 records from Royal Botanic Garden Edinburgh Herbarium (E). 9378 records from tan-database. 3716 records from All observations extracted from the Flora of Northumberland and Durham 1831. 2357 records from Herbarium J Räsänen. 4086 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 700754 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from Macrobenthos Chukchi Sea, 1986. 64723 records from Michigan State University Herbarium Vascular Plants. 142 records from Filogeografía y recursos genéticos de las vainillas de México. 1429 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 1490 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 3944 records from Estudio florístico de la Sierra de Pachuca, Hidalgo, México. 331 records from Forster herbarium, Göttingen (GOET). 291215 records from Botany (UPS). 1206 records from Aves Collection of Institute of Systematics and Evolution of Animals. 1848 records from European Molecular Biology Laboratory Australian Mirror. 395580 records from Instituto de Ciencias Naturales. 329 records from Microbial Culture Collection, National Institute for Environmental Studies. 12 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 33546 records from LNHG Biological Records Dataset. 3083 records from Medicinial plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2994 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4058 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 511 records from English Nature Berkshire Staff Surveys 1990's. 101220 records from Merseyside BioBank (verified). 3683 records from CNMT - Herbário Centro Norte Mato Grossense. 10373 records from Type herbarium, Göttingen (GOET). 1 records from Collection botanique Letendre (abbé) (BOUM). 355 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 1275 records from Seasearch Marine Surveys in the Isle of Man. 333153 records from National Forest Inventory (SLU). 93601 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 617 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 17 records from Levantamento de Herbáceas do PARNA Jaú. 27282 records from HAS - Herbário Alarich Rudolf Holger Schultz. 908 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 1 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 426 records from Species composition in twelve (12) Afzelia africana Sm & Pers populations in Benin. Data mobilized in the framework of the BID-AF2015-0030-SMA project of Isidore Amahowe. 4373 records from Inventario Florístico de la Reserva de la Biósfera La Sepultura del Corredor Biológico Sierra Madre del Sur. Fase II. 36164 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 3037 records from SMNS Palaeontological collection - Fossil plants. 4 records from Towards a revision of the genus Vitex L. (Lamiaceae) in Madagascar I: a distinctive new species from Northeastern Madagascar. 4613 records from Estado actual y fitogeografía de las especies de la Familia Cucurbitaceae endémicas de México. 208 records from Thistles damage. 442 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 78110 records from Vascular plant diversity in forests. 4673 records from Estonian Nature Observations Database. 1032 records from Geneva
Keywords: GBIF; biodiversity; species occurrences